Chemically strengthened lithium disilicate-lithium metasilicate glass-ceramic

CN123003160APending Publication Date: 2026-10-30CORNING INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611029135.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-11-13
Filing Date
2019-11-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

富含钠的表面层还表现出低的化学耐久性,导致玻璃陶瓷易受到优先蚀刻、点蚀和其他表面损伤

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003160A_ABST
    Figure CN123003160A_ABST
Patent Text Reader

Abstract

The ion exchanged glass-ceramic articles described herein have a stress that decreases from compressive stress to tensile stress as a function of distance according to a substantially linear function from a depth of about 0.07 t to a depth of about 0.26 t of the outer surface of the ion exchanged glass-ceramic article. The stress transitions from compressive stress to tensile stress at a depth of about 0.18 t to about 0.25 t of the outer surface of the ion exchanged glass-ceramic article. The absolute value of the maximum compressive stress at the outer surface of the ion exchanged glass article is 1.8 to 2.2 times the absolute value of the maximum central tension (CT) of the ion exchanged glass article, and the glass-ceramic article has a fracture toughness greater than or equal to 1 MPaVm as measured according to the double cantilever beam method.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the patent application filed on November 12, 2019, with application number 201980020541.1 and entitled "Chemically Strengthened Lithium Pyrosilicate-Lithium Feldspar Glass-Ceramic". Cross-references to related applications

[0002] This application claims priority and benefit to U.S. Provisional Application No. 62 / 760,753, filed November 13, 2018, entitled “Chemically Strengthened Lithium Disilicate-Petalite Glass-Ceramics,” the entire contents of which are incorporated herein by reference. Technical Field

[0003] This specification generally relates to glass articles, and more specifically to glass-ceramic articles with improved chemical durability and damage resistance, and methods for forming thereof. Background Technology

[0004] When glass-ceramics with a lithium pyrosilicate crystalline phase undergo a conventional ion exchange process, a sodium-rich, low-refractive-index layer forms on the surface of the glass-ceramic. The presence of this sodium-rich surface layer makes the glass-ceramic surface susceptible to subsurface hydration, which can lead to the growth of sodium carbonate crystals on the glass-ceramic surface, resulting in surface haziness. The sodium-rich surface layer also exhibits low chemical durability, making the glass-ceramic susceptible to preferential etching, pitting, and other surface damage.

[0005] In addition to altering the properties of the glass-ceramic, the presence of a low-refractive-index layer can blur the images generated during FSM imaging, making the quality control of ion exchange processes using these images unreliable.

[0006] Therefore, there is a need for glass-ceramic products with improved chemical durability and damage resistance, as well as methods for improving quality control in ion exchange processes. Summary of the Invention

[0007] According to the first aspect disclosed herein, an ion-exchange glass-ceramic product has a thickness t The glass article includes stress, which, according to a fundamental linear function, originates from the outer surface of the ion-exchange glass-ceramic article towards the centerline, from approximately 0.07... t The depth is approximately 0.26. t The depth decreases with increasing distance; the stress is approximately 0.18 meters from the outer surface of the ion-exchange glass-ceramic product. t To approximately 0.25 tAt a depth of [insert depth here], the stress changes from compressive stress to tensile stress; and the absolute value of the maximum compressive stress at the outer surface of the ion-exchange glass-ceramic article is 1.8 to 2.2 times the absolute value of the maximum central tension (CT) of the ion-exchange glass-ceramic article; and the fracture toughness of the ion-exchange glass-ceramic article is greater than or equal to 1 MPa√m, as measured by the double cantilever beam method.

[0008] According to the second aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to the first aspect, wherein the maximum central tension is greater than or equal to 70 MPa.

[0009] According to the third aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any of the preceding aspects, wherein the maximum central tension is 80 MPa to 140 MPa.

[0010] According to the fourth aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any of the preceding aspects, wherein the maximum compressive stress is from 180 MPa to 350 MPa.

[0011] According to the fifth aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any of the preceding aspects, wherein the fracture toughness is from 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.

[0012] According to the sixth aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any of the preceding aspects, wherein the Na2O concentration at the outer surface of the ion-exchange glass-ceramic article is less than 10 mol.

[0013] According to the seventh aspect disclosed herein, an ion-exchange glass-ceramic product has a thickness t The following parameters are specified: Li ion concentration increases from surface Li ion concentration to maximum Li ion concentration with increasing distance from the outer surface of the ion-exchange glass-ceramic product, wherein the difference between surface Li ion concentration and maximum Li ion concentration is less than 5 mol%; Na ion concentration increases from surface Na ion concentration and then decreases to minimum Na ion concentration with increasing distance from the outer surface of the ion-exchange glass-ceramic product, wherein the difference between surface Na ion concentration and minimum Na ion concentration is less than 5 mol%, and surface Na ion concentration is less than 10 mol%; and the fracture toughness of the ion-exchange glass-ceramic product is greater than 1 MPa√m, as measured by the double cantilever beam method.

[0014] According to the eighth aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to the seventh aspect, wherein, throughout the entire thickness of the ion-exchange glass-ceramic article... t In this case, the Na ion concentration is greater than 0 moles.

[0015] According to the ninth aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to the seventh or eighth aspect, wherein the Na ion concentration is greater than 0 mol% and less than 2.5 mol%.

[0016] According to the 10th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 7th to 9th aspects, wherein the maximum concentration of Li ions is 19 mol% to 32 mol%.

[0017] According to the 11th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 7th to 10th aspects, wherein the fracture toughness is from 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.

[0018] According to the 12th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 7th to 11th aspects, which further comprises more than 0 mol% to 6 mol% of Al2O3.

[0019] According to the 13th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 7th to 12th aspects, which further comprises 0.7 mol% to 2.2 mol% of P2O5.

[0020] According to the 14th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 7th to 13th aspects, which further comprises 1.7 mol% to 4.5 mol% ZrO2.

[0021] According to the 15th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of aspects 7 to 14, which further comprises 60 mol% to 72 mol% of SiO2.

[0022] According to the 16th aspect disclosed herein, an ion-exchange glass-ceramic article comprises 1% to 30% residual glass content and 70% to 99% crystalline phase, said crystalline phase being selected from lithium pyrosilicate, petalite, β-quartz, β-spodumene solid solutions, and combinations thereof; said ion-exchange glass-ceramic article has a thickness t and includes stress, said stress decreasing with increasing distance from the outer surface of the ion-exchange glass-ceramic article toward a centerline, wherein the stress decreases from approximately 0.07 meters from the outer surface of the ion-exchange glass-ceramic article... t The depth is approximately 0.26. t The stress decreases according to a fundamental linear function at a depth of approximately 0.18 meters from the outer surface of the ion-exchange glass-ceramic article. t To approximately 0.25 t At a depth of [insert depth here], the stress changes from compressive stress to tensile stress; and the maximum compressive stress at the outer surface of the ion-exchange glass article is 1.8 to 2.2 times the value of the maximum central tension (CT) of the ion-exchange glass article.

[0023] According to the 17th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to the 16th aspect, wherein the fracture toughness of the ion-exchange glass-ceramic article is from 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.

[0024] According to the 18th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to the 16th or 17th aspect, wherein the ion-exchange glass-ceramic is opaque.

[0025] According to the 19th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 16th to 18th aspects, wherein the maximum compressive stress is 180 MPa to 350 MPa.

[0026] According to the 20th aspect disclosed herein, the ion-exchange glass-ceramic article includes the ion-exchange glass-ceramic article according to any one of the 16th to 19th aspects, wherein the Na2O concentration at the outer surface of the ion-exchange glass-ceramic article is less than 10 mol.

[0027] According to the 21st aspect disclosed herein, a method for strengthening a glass-ceramic article having a crystalline phase selected from lithium feldspar, lithium pyrosilicate, and combinations thereof, the method comprising: applying an ion-exchange medium to the glass-ceramic article, wherein the ion-exchange medium comprises greater than 0 wt% and less than or equal to 20 wt% of NaNO3, 80 wt% to less than 100 wt% of KNO3, and 0.01 wt% to 0.5 wt% of LiNO3.

[0028] According to the 22nd aspect disclosed herein, the method includes the method according to the 21st aspect, wherein the temperature of the ion exchange medium is 380 °C to 550 °C.

[0029] According to the 23rd aspect disclosed herein, the method includes the method according to the 21st or 22nd aspect, wherein an ion exchange medium is applied to the glass-ceramic article for a period of 2 hours to 16 hours.

[0030] According to the 24th aspect disclosed herein, the method includes the method according to any one of the 21st to 23rd aspects, wherein the ion exchange medium is a second ion exchange medium, and the method further includes: applying a first ion exchange medium to a glass-ceramic article, wherein the first ion exchange medium comprises NaNO3, KNO3 and 0.01 wt% to 0.5 wt% LiNO3, and applying a second ion exchange medium after applying the first ion exchange medium.

[0031] According to the 25th aspect disclosed herein, the method includes the method according to the 24th aspect, wherein the first ion exchange medium comprises more than 20% by weight of NaNO3.

[0032] According to the 26th aspect disclosed herein, the method includes the method according to the 24th or 25th aspect, wherein the second ion exchange medium comprises more than 95% by weight and less than 100% by weight of KNO3 and more than 0% by weight and less than 5% by weight of NaNO3.

[0033] According to the 27th aspect disclosed herein, a method for strengthening a glass-ceramic article having a crystalline phase selected from lithium feldspar, lithium pyrosilicate, and combinations thereof, the method comprising: applying an ion-exchange medium to the glass-ceramic article, wherein the ion-exchange medium comprises greater than 20 wt% and less than or equal to 50 wt% of NaNO3, 50 wt% to less than 80 wt% of KNO3, and 0.01 wt% to 0.5 wt% of LiNO3.

[0034] According to the 28th aspect disclosed herein, the method includes the method according to the 27th aspect, wherein the temperature of the ion exchange medium is 380 °C to 550 °C.

[0035] According to aspect 29 disclosed herein, the method includes the method according to aspect 27 or 28, wherein an ion exchange medium is applied to the glass-ceramic article for a period of 2 hours to 16 hours.

[0036] According to the 30th aspect disclosed herein, the method comprises the method according to any one of the 27th to 29th aspects, wherein the ion exchange medium comprises 30 wt% to 50 wt% NaNO3 and 50 wt% to 70 wt% KNO3.

[0037] According to the 31st aspect disclosed herein, a consumer electronic product includes a housing comprising a front surface, a rear surface, and a side surface; electrical components at least partially located within the housing, the electrical components including a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; and a cover substrate disposed above the display, wherein at least one of the housing or cover substrate comprises an ion-exchange glass-ceramic article as described in any one of aspects 1 to 20.

[0038] Further features and advantages are set forth in the following detailed description, some of which will be apparent to those skilled in the art from the description, or will be recognized by practicing the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings.

[0039] It should be understood that the foregoing general description and the following detailed description both depict various embodiments and are intended to provide an overall assessment or framework for understanding the nature and characteristics of the claimed subject matter. The included drawings provide a further understanding of the various embodiments and are incorporated in and form a part of this specification. The drawings illustrate the various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter.

[0040] This application also includes the following implementation schemes.

[0041] 1. An ion-exchange glass-ceramic product having a thickness of t ,in: The glass article includes stress, which is based on a fundamental linear function, at approximately 0.07 from the outer surface of the ion-exchange glass-ceramic article towards the centerline. t The depth is approximately 0.26. t The depth decreases as the distance increases; The stress is located at a distance of approximately 0.18 meters from the outer surface of the ion-exchange glass-ceramic product. t To approximately 0.25 t At a depth where compressive stress changes to tensile stress; and The absolute value of the maximum compressive stress at the outer surface of ion-exchange glass-ceramic products is 1.8 to 2.2 times the absolute value of the maximum central tension (CT) of the ion-exchange glass-ceramic products; and The fracture toughness of ion-exchange glass-ceramic products is greater than or equal to 1 MPa√m, as measured by the double cantilever beam method. 2. The ion-exchange glass-ceramic product according to embodiment 1, wherein the maximum central tension is greater than or equal to 70 MPa.

[0042] 3. The ion-exchange glass-ceramic product according to embodiment 1, wherein the maximum central tension is 80 MPa to 140 MPa.

[0043] 4. The ion-exchange glass-ceramic article according to any one of embodiments 1-3, wherein the maximum compressive stress is 180 MPa to 350 MPa.

[0044] 5. An ion-exchange glass-ceramic article according to any one of embodiments 1-4, wherein the fracture toughness is from 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.

[0045] 6. The ion-exchange glass-ceramic article according to any one of embodiments 1-5, wherein the Na2O concentration at the outer surface of the ion-exchange glass-ceramic article is less than 10 mol.

[0046] 7. An ion-exchange glass-ceramic product having a thickness of t ,in: The Li ion concentration increases from the surface Li ion concentration to the maximum Li ion concentration with increasing distance from the outer surface of the ion-exchange glass-ceramic product, with the difference between the surface Li ion concentration and the maximum Li ion concentration being less than 5 mol%. The Na ion concentration increases with increasing distance from the outer surface of the ion-exchange glass-ceramic product, then decreases to a minimum Na ion concentration, wherein the difference between the surface Na ion concentration and the minimum Na ion concentration is less than 5 mol%, and the surface Na ion concentration is less than 10 mol%. The fracture toughness of ion-exchange glass-ceramic products is greater than 1 MPa√m, as measured by the double cantilever beam method.

[0047] 8. The ion-exchange glass-ceramic article according to embodiment 7, wherein, throughout the entire thickness of the ion-exchange glass-ceramic article... t In this case, the concentration of Na ions is greater than 0 moles.

[0048] 9. The ion-exchange glass-ceramic product according to embodiment 8, wherein the concentration of Na ions is greater than 0 mol% and less than 2.5 mol%.

[0049] 10. The ion-exchange glass-ceramic article according to any one of embodiments 7-9, wherein the maximum concentration of Li ions is from 19 mol% to 32 mol%.

[0050] 11. The ion-exchange glass-ceramic article according to any one of embodiments 7-10, wherein the fracture toughness is from 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.

[0051] 12. The ion-exchange glass-ceramic article according to any one of embodiments 7-11, further comprising more than 0 mol% to 6 mol% of Al2O3.

[0052] 13. The ion-exchange glass-ceramic article according to any one of embodiments 7-12, further comprising 0.7 mol% to 2.2 mol% of P2O5.

[0053] 14. The ion-exchange glass-ceramic article according to any one of embodiments 7-13, further comprising 1.7 mol% to 4.5 mol% ZrO2.

[0054] 15. The ion-exchange glass-ceramic article according to any one of embodiments 7-14, further comprising 60 mol% to 72 mol% of SiO2.

[0055] 16. An ion-exchange glass-ceramic product comprising 1% to 30% residual glass content and 70% to 99% crystalline phase, said crystalline phase being selected from lithium pyrosilicate, petalite, β-quartz, β-spodumene solid solutions, and combinations thereof; said ion-exchange glass-ceramic product having a thickness of t And includes stress, which decreases as the distance from the outer surface of the ion-exchange glass-ceramic article towards the centerline increases, wherein: From a distance of approximately 0.07 meters from the outer surface of the ion-exchange glass-ceramic product t The depth is approximately 0.26. t The stress decreases according to a fundamental linear function at the depth of the stress. The stress is located at a distance of approximately 0.18 meters from the outer surface of the ion-exchange glass-ceramic product. t To approximately 0.25 t At a depth where compressive stress changes to tensile stress; and The maximum compressive stress on the outer surface of ion-exchange glass products is 1.8 to 2.2 times the value of the maximum central tension (CT) of the ion-exchange glass products.

[0056] 17. The ion-exchange glass-ceramic article according to embodiment 16, wherein the fracture toughness of the ion-exchange glass-ceramic article is from 1 MPa√m to 1.5 MPa√m, as measured by the double cantilever beam method.

[0057] 18. The ion-exchange glass-ceramic article according to embodiment 16 or embodiment 17, wherein the ion-exchange glass-ceramic is opaque.

[0058] 19. The ion-exchange glass-ceramic article according to any one of embodiments 16-18, wherein the maximum compressive stress is 180 MPa to 350 MPa.

[0059] 20. The ion-exchange glass-ceramic article according to any one of embodiments 16-19, wherein the Na2O concentration at the outer surface of the ion-exchange glass-ceramic article is less than 10 mol.

[0060] 21. A method for strengthening a glass-ceramic article having a crystalline phase selected from lithium feldspar, lithium pyrosilicate, and combinations thereof, the method comprising: An ion exchange medium is applied to a glass-ceramic article, wherein the ion exchange medium comprises greater than 0 wt% and less than or equal to 20 wt% of NaNO3, 80 wt% to less than 100 wt% of KNO3, and 0.01 wt% to 0.5 wt% of LiNO3.

[0061] 22. The method as described in embodiment 21, wherein the temperature of the ion exchange medium is 380 °C to 550 °C.

[0062] 23. The method of embodiment 22, wherein an ion exchange medium is applied to the glass-ceramic article for a period of 2 hours to 16 hours.

[0063] 24. The method according to any one of embodiments 21-23, wherein the ion exchange medium is a second ion exchange medium, and the method further comprises: A first ion exchange medium is applied to a glass-ceramic article, wherein the first ion exchange medium comprises NaNO3, KNO3 and 0.01 wt% to 0.5 wt% LiNO3, and a second ion exchange medium is applied after the first ion exchange medium is applied.

[0064] 25. The method of embodiment 24, wherein the first ion exchange medium contains more than 20% by weight of NaNO3.

[0065] 26. The method of embodiment 24 or embodiment 25, wherein the second ion exchange medium comprises more than 95% by weight and less than 100% by weight of KNO3 and more than 0% by weight and less than 5% by weight of NaNO3.

[0066] 27. A method for strengthening a glass-ceramic article having a crystalline phase selected from lithium feldspar, lithium pyrosilicate, and combinations thereof, the method comprising: An ion exchange medium is applied to a glass-ceramic article, wherein the ion exchange medium comprises more than 20% by weight and less than or equal to 50% by weight of NaNO3, 50% by weight to less than 80% by weight of KNO3, and 0.01% by weight to 0.5% by weight of LiNO3.

[0067] 28. The method as described in embodiment 27, wherein the temperature of the ion exchange medium is 380 °C to 550 °C.

[0068] 29. The method of embodiment 28, wherein an ion exchange medium is applied to the glass-ceramic article for a period of 2 hours to 16 hours.

[0069] 30. The method of any one of embodiments 27-29, wherein the ion exchange medium comprises 30% to 50% by weight of NaNO3 and 50% to 70% by weight of KNO3.

[0070] 31. A consumer electronics product comprising: A housing, the housing including a front surface, a rear surface and side surfaces; Electrical components, at least partially located within the housing, including a controller, a memory, and a display, the display being located on or near the front surface of the housing; and A cover plate substrate, which is disposed above the display. Wherein, a portion of the housing or at least one of the cover plate substrate comprises an ion-exchange glass-ceramic article as described in any one of embodiments 1-6. Brief description of the attached figures Figure 1 This is a graph showing the change in the concentration (Y-axis, in mol% of oxides) of sodium, lithium and potassium elements in a glass-ceramic substrate formed from composition A as a function of conventional ion exchange treatment, based on the depth from the surface to the sample thickness (X-axis, in micrometers or µm). Figure 2A and 2B This is the FSM spectrum of a glass-ceramic product that has undergone conventional ion exchange treatment at 365 mm. Figure 3 It has Figure 1 Optical micrographs of the elemental distribution of glass-ceramic products after exposure to 85 ℃ / 85% relative humidity for 48 hours; Figure 4A These are atomic force microscopy (AFM) images of the surface roughness of a glass sample consistent with Example A; Figure 4B This is an AFM image of the surface roughness of a glass-ceramic article formed from composition A after undergoing conventional ion exchange treatment; Figure 5 This is an FSM pattern at 365 nm of a glass-ceramic article subjected to stripeless ion exchange treatment according to one or more embodiments shown and described herein; Figure 6 This is a graph showing how the delay (left Y-axis, in degrees) and stress (right Y-axis, in megapascals (MPa), where compressive stress is positive and tensile stress is negative) of a glass-ceramic article subjected to stripeless ion exchange treatment vary with respect to the thickness (X-axis, in micrometers or µm) from the surface to the sample thickness, according to one or more embodiments shown and described herein. Figure 7 This is a graph showing the dimensional growth (Y-axis, in length %) of glass-ceramic articles subjected to stripeless ion exchange treatment in relation to center tension (X-axis; in MPa) according to one or more embodiments shown and described herein. Figures 8A-8E This is the FSM pattern at 365 nm of a glass-ceramic article subjected to single-stripe ion exchange treatment according to one or more embodiments shown and described herein; Figure 9 This is a graph showing how the concentrations (Y-axis, in mol% of oxides) of sodium, lithium, and potassium elements in a glass-ceramic substrate formed from composition A vary with depth (X-axis, in micrometers or µm) from the surface to the sample thickness when the substrate is subjected to a single-stripe ion exchange treatment according to one or more embodiments shown and described herein. Figures 10A-10H This is the FSM pattern at 365 nm of a glass-ceramic article subjected to single-stripe ion exchange treatment according to one or more embodiments shown and described herein; Figure 11 This is a graph showing the variation of stress (Y-axis, in MPa; compressive stress is positive and tensile stress is negative) of glass-ceramic articles subjected to single-stripe ion exchange treatment, measured using RNF, according to one or more embodiments shown and described herein, as a function of depth (X-axis, in micrometers or µm) from the surface to the sample thickness. Figure 12This is a graph showing the variation of stress (Y-axis, in MPa; compressive stress is positive and tensile stress is negative) of glass-ceramic articles subjected to stripeless ion exchange treatment, measured using RNF, according to one or more embodiments shown and described herein, as a function of depth (X-axis, in micrometers or µm) from the surface to the sample thickness. Figure 13 It is a graph of the applied fracture stress (Y-axis; in MPa) of a sample (X-axis) after undergoing various ion exchange treatments according to one or more embodiments shown and described herein and after damage has been introduced with 80 grit sandpaper. Figures 14A-14C This is a graph of the results of asymptotic surface drop tests on samples (X-axis) subjected to various ion exchange treatments according to one or more embodiments shown and described herein, wherein the failure height is shown on the Y-axis (in cm). Figure 15A These are optical micrographs of glass-ceramic products that have undergone conventional ion exchange treatment before being exposed to aging conditions at 85 °C / 85% relative humidity. Figure 15B yes Figure 15A Optical micrographs of glass-ceramic products after 144 hours of exposure to aging conditions of 85 °C / 85% relative humidity; Figure 15C Optical micrographs of glass-ceramic articles subjected to one or more embodiments shown and described herein after exposure to aging conditions of 85 °C / 85% relative humidity for 48 hours. Figure 15D yes Figure 15C Optical micrographs of glass-ceramic products after 144 hours of exposure to aging conditions of 85 °C / 85% relative humidity; Figure 16A yes Figure 15B A graph showing the distribution of carbon, hydrogen, Li2O, Na2O, Al2O3 and P2O5 elemental concentrations (Y-axis, in mol% of oxides) in a glass-ceramic substrate as a function of depth from the surface to the sample thickness (X-axis, in micrometers or µm). Figure 16B yes Figure 15D A graph showing the distribution of carbon, hydrogen, Li2O, Na2O, Al2O3 and P2O5 elemental concentrations (Y-axis, in mol% of oxides) in a glass-ceramic substrate as a function of depth from the surface to the sample thickness (X-axis, in micrometers or µm). Figure 17 This is a schematic diagram of the setup used in the double cantilever beam method for measuring fracture toughness; Figure 18AIt is a plan view of an exemplary electronic device containing any reinforced article disclosed herein; and Figure 18B yes Figure 18A A perspective view of an exemplary electronic device. Detailed Implementation

[0071] The various embodiments will now be described in detail, examples of which are illustrated in the accompanying drawings. Wherever possible, the same reference numerals are used in the drawings to denote the same or similar parts.

[0072] Definition and measurement techniques In this document, a range may be expressed as beginning "about" a specific value and / or ending "about" another specific value. When such a range is expressed, another implementation includes beginning with and / or ending with said specific value. Similarly, when a value is expressed as an approximation using the antecedent "about," it should be understood that the specific value constitutes another implementation. It should also be understood that the endpoints of each range are significant both in relation to and independent of the other endpoint. When such a range is expressed, an implementation includes beginning with and / or ending with another specific value. Similarly, when a value is expressed as an approximation using the antecedent "about," it should be understood that the specific value constitutes another implementation. Regardless of whether the values ​​or endpoints of a range in the specification are stated using "about," the values ​​or endpoints of a range are intended to include two implementations: one modified by "about" and another not modified by "about." It should also be understood that the endpoints of each range are significant both in relation to and independent of the other endpoint.

[0073] As used herein, the terms “substantially,” “basically,” and their variations are intended to mean that a described feature is equal to or approximately equal to a numerical value or description. For example, a “substantially flat” surface is intended to mean a flat or generally flat surface. Furthermore, as defined above, “substantially similar” is intended to mean that two values ​​are equal or approximately equal. In some embodiments, “substantially similar” may mean values ​​that differ from each other by about 10%, for example, by about 5%, or by about 2%.

[0074] The directional terms used in this article—such as up, down, right, left, front, back, top, bottom—are only for reference to the accompanying drawings and are not intended to imply absolute orientation.

[0075] The disclosed scope should be understood to include any and all sub-scopes or any and all individual values ​​contained within each scope, and to support claims describing such sub-scopes or individual values. For example, the stated range of 1 to 10 should be understood to include any and all sub-scopes between the minimum value of 1 and the maximum value of 10, or individual values ​​between them (including and / or excluding endpoints), and to support claims describing such sub-scopes or individual values; that is, all sub-scopes that begin with a minimum value of 1 or a greater value and end with a maximum value of 10 or a smaller value (e.g., 5.5 to 10, 2.34 to 3.56, etc.) or any value from 1 to 10 (e.g., 3, 5.8, 9.9994, etc.).

[0076] As used herein, “compression depth” or “DOC” refers to the depth of the compressive stress (CS) layer, which is the depth at which the stress within a glass-ceramic article changes from compressive stress to tensile stress, and where the stress value is zero. Compressive stress is expressed here as positive (>0) stress, and tensile stress as negative (<0) stress. However, unless otherwise stated, tensile and compressive stress values ​​are expressed as positive or absolute values ​​in this specification. Depending on the ion exchange treatment method, DOC can be measured using an FSM or a Scattered Aperture Polarizing Mirror (SCALP). If the stress in the glass article is generated by exchanging potassium ions into the glass article, DOC is measured using an FSM. If the stress is generated by exchanging sodium ions into the glass article, DOC is measured using a SCALP. If the stress in a glass product is generated by the exchange of both potassium and sodium ions into the glass, the DOC is measured by SCALP, because the exchange depth of sodium is considered to represent the DOC, while the exchange depth of potassium ions represents the magnitude of the change in compressive stress (but not the change from compressive stress to tensile stress); the exchange depth of potassium ions in such glass products is measured by FSM.

[0077] The various embodiments described herein, particularly the compressive stress, are measured using a surface stress meter (FSM) employing a commercial instrument such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd., Japan. As will be discussed in more detail herein, surface stress measurement relies on the accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass-ceramic. The SOC is then measured according to Scheme C (glass disk method) of the ASTM standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," the contents of which are incorporated herein by reference in their entirety. If a low-refractive-index layer is formed, the surface compressive stress (and the compressive stress of the low-refractive-index layer) is measured by the birefringence of the first transmission (coupling) resonance of the low-refractive-index layer in a prism-coupled measurement, and the layer depth of the low-refractive-index layer is measured by the spacing between the first and second transmission resonances or the width of the first transmission resonance.

[0078] The stress distribution curve from approximately the knee to the maximum CT value can be obtained using the refractive near-field (RNF) method as described in U.S. Patent No. 8,854,623, entitled "Systems and methods for measuring a profile characteristic of a glass sample," which is incorporated herein by reference in its entirety. This RNF curve is force-balanced and calibrated to the maximum center tension (also known as peak center tension) value provided by SCALP measurements. Specifically, the RNF method includes placing the glass article near a reference block, generating a polarization-switched beam that switches between orthogonal polarizations at frequencies from 1 Hz to 50 Hz, measuring the power in the polarization-switched beam, and generating a polarization-switched reference signal, wherein the power measured in each orthogonal polarization differs from each other by less than 50%. The method also includes transmitting the polarization-switched beam through the glass sample and the reference block to different depths within the glass sample, then using a relay optics system to transmit the transmitted polarization-switched beam to a signal photodetector, which generates a polarization-switched detector signal. The method also includes dividing the detector signal by the reference signal to form a normalized detector signal, and determining the distribution curve characteristics of the glass sample from the normalized detector signal.

[0079] The stress distribution curve can be plotted using a combination of RNF, SCALP, and FSM. FSM is used to plot the portion of the stress distribution curve near the surface, while RNF, together with SCALP, is used to plot the shape of the tensile stress portion of the stress distribution curve beyond the knee depth. The portions obtained from FSM, RNF, and SCALP are stitched together to provide a complete stress distribution curve plot as shown below. RNF is force-balanced and calibrated to match the SCALP center tension. Force balancing is performed by moving the neutral axis to match the tensile stress region below the neutral axis in the plot with the compressive stress region above the neutral axis. After force balancing and calibration of RNF, the surface peak plot obtained from FSM is stitched into the RNF plot of the distribution curve, replacing the corresponding RNF plot portion. The process of force balancing, calibration to SCALP center tension, and stitching is repeated until convergence is achieved, meaning the distribution curve plot essentially does not change with further repetitions. Standard smoothing techniques can be used, where appropriate and necessary, to remove measurement noise.

[0080] The concentration distribution of various components in the glass, such as alkali metal components, is measured by electron probe microanalysis (EPMA). For example, EPMA can be used to identify compressive stress in the glass caused by alkali metal ion exchange into the glass. In some embodiments, glow discharge photoemission spectroscopy (GdOES) is used to measure the average surface concentration level (e.g., the average surface concentration level within 100 nm of the glass surface).

[0081] Fracture toughness measurements were performed using the double cantilever beam (DCB) method. The geometry of the DCB specimen is shown in [Figure / Image]. Figure 17 The key parameters are crack length a, applied load P, cross-sectional dimensions w and 2h, and the thickness of the crack guiding groove. b The samples were formed from the same composition as the samples to be tested, but without undergoing ion exchange. They were prepared by cutting glass into rectangles with a width of 2h = 1.25 cm and a thickness ranging from w = 0.3 mm to 1 mm, and a total sample length varying from 5 cm to 10 cm. Each glass sample had holes drilled at both ends with diamond bits to provide a means of attaching the sample to a sample holder and load. Cracks “guide grooves” were cut along the length of the sample on two flat surfaces using a wafer saw with diamond blades. b This leaves the material's "web," which is about half the total plate thickness. Figure 17 In bThe 180 μm height represents the blade thickness or kerf. The high dimensional tolerance of the saw minimizes variations between samples. The saw is also used to cut initial cracks of a = 15 mm, which creates an extremely thin wedge of material near the crack tip (due to the blade curvature), making it easier to initiate cracks in the sample.

[0082] Crack guide groove b The crack is kept in-plane and prevented from growing away from the crack plane. The sample is mounted in a metal sample holder by hooking a wire into the bottom hole of the sample. The sample is also supported at the opposite ends to keep it level under low load conditions. A spring connected in series with a force sensor (FUTEK, LSB200) is hooked into the top hole, and then a rope and high-precision track are used to gradually apply the load. The crack is monitored using a microscope (5–10 μm resolution) connected to a digital camera and computer.

[0083] By maintaining tight tolerances for dimensional parameters, the applied stress intensity K is calculated using the following equation (1). P The input parameters are shown in Figure 17 : (1) For each sample, a crack is initiated at the tip of the web, and the initial crack is then carefully allowed to grow under subcritical conditions until the ratio of size a / h is greater than 1.5. This ratio is used in equation (1) to accurately calculate the stress intensity. At this point, the crack length a is measured and recorded using a 5 μm resolution movable display mirror. A drop of toluene is then dropped into the crack groove and wicked along the entire length of the groove under capillary force, preventing crack movement unless the fracture toughness is applied. Toluene, heavy mineral oil, silicone oil, and other organic substances act as a barrier between atmospheric moisture and the glass surface and prevent subcritical crack growth. The load is then increased until the sample fractures, and the critical stress intensity is calculated based on the failure load and sample size. All samples are measured using optical microscopy after testing to ensure that the correct sample size is used in the K calculation. When testing the fracture toughness of ion-exchanged samples, the measurements are performed on samples with the same composition as the sample to be tested, but the sample to be tested has undergone ion exchange prior to this measurement.

[0084] The term "formed from" can mean one or more of the following: containing, substantially composed of, or consisting of. For example, a component formed from a particular material can contain that particular material, consist substantially of that particular material, or consist of that particular material.

[0085] Overview of glass and ceramic products The glass-ceramic articles of various embodiments include lithium feldspar and lithium pyrosilicate as the main crystalline phases, and optionally further include a lithium aluminum silicate (LAS) crystalline phase. The glass-ceramic articles include a surface layer having a sodium content of less than or equal to 10 mol%. After ion exchange treatment, the glass-ceramic articles described herein exhibit increased energy storage (central tension), increased fracture toughness, and are less prone to breakage.

[0086] Lithium feldspar (LiAlSi4O) 10 Lithium pyrosilicate (Li₂Si₂O₅) is a monoclinic crystal with a three-dimensional framework and a layered structure, wherein the layered structure has folded Si₂O₅ layers connected by Li and Al tetrahedra. Li is tetrahedral coordinated with oxygen. Lithium pyrosilicate is a lithium source and is used as a low thermal expansion phase to improve the thermal shock resistance of glass ceramics or ceramic components. Lithium pyrosilicate is an orthorhombic crystal based on a wave-like array of {Si₂O₅} tetrahedra. The crystal is typically plate-like or lath-like in shape with prominent cleavage planes. Due to its randomly oriented interlocking crystal microstructure, lithium pyrosilicate-based glass ceramics exhibit highly desirable mechanical properties, including high bulk strength and fracture toughness. This crystal structure forces cracks to propagate through the material via a tortuous path around the interlocking crystals, thereby improving strength and fracture toughness.

[0087] There are two major families of lithium pyrosilicate glass ceramics. The first group includes lithium pyrosilicate glass ceramics doped with cerium dioxide and noble metals (such as silver). They can be photosensitively nucleated by ultraviolet light, followed by heat treatment to produce robust glass ceramics, such as Fotoceram®. The second family of lithium pyrosilicate glass ceramics is nucleated by the addition of P2O5, where the nucleating phase is Li3PO4. P2O5-nucleated lithium pyrosilicate glass ceramics have been developed for a wide variety of applications, such as high-temperature sealing materials, hard disks for computer hard drives, transparent armor, and dental applications.

[0088] The glasses and glass-ceramics described herein can generally be described as lithium-containing aluminosilicate glasses or glass-ceramics, and include SiO2, Al2O3, and Li2O. In addition to SiO2, Al2O3, and Li2O, the glasses and glass-ceramics specifically described herein may further contain alkali metal oxides, such as Na2O, K2O, Rb2O, or Cs2O, as well as P2O5 and ZrO2, and various other components as described below. In one or more embodiments, the crystalline phase includes pyroclastic feldspar and lithium pyrosilicate, but depending on the composition of the precursor glass, β-spodumene solid solution, β-quartz, metasilicates, lithium phosphate, and zirconium may also be present. In some embodiments, the residual glass content of the glass-ceramic composition is 1 to 30 wt%, 1 to 25 wt%, 1 to 20 wt%, 1 to 15 wt%, 1 to 10 wt%, 1 to 5 wt%, 5 to 30 wt%, 5 to 25 wt%, 5 to 20 wt%, 5 to 15 wt%, 5 to 10 wt%, 10 to 30 wt%, 10 to 25 wt%, 10 to 20 wt%, 10 to 15 wt%, 15 to 30 wt%, 15 to 25 wt%, 15 to 20 wt%, 20 to 30 wt%, 20 to 25 wt%, or 25 to 30 wt%, as determined by Rietveld analysis of the XRD pattern. It should be understood that the residual glass content can be within a subrange formed by any and all of the foregoing endpoints. Therefore, in some embodiments, the glass-ceramic article has 70 to 99 wt%, 70 to 95 wt%, 70 to 90 wt%, 70 to 85 wt%, 70 to 80 wt%, 70 to 75 wt%, 75 to 99 wt%, 75 to 95 wt%, 75 to 90 wt%, 75 to 85 wt%, 75 to 80 wt%, 80 to 99 wt%, 80 to 95 wt%, 80 to 85 wt%, 85 to 99 wt%, 85 to 95 wt%, 85 to 90 wt%, 90 to 99 wt%, or 95 to 99 wt% of crystalline phase.

[0089] SiO2 is the primary glass-forming agent, which stabilizes the network structure of glass and glass-ceramics. In some embodiments, the glass or glass-ceramic composition contains 55 to 80 mol% SiO2. In some embodiments, the glass or glass-ceramic composition contains 60 to 72 mol% SiO2. In some embodiments, the glass or glass-ceramic composition may contain 55 to 80 mol%, 55 to 77 mol%, 55 to 75 mol%, 55 to 73 mol%, 60 to 80 mol%, 60 to 77 mol%, 60 to 75 mol%, 60 to 73 mol%, 60 to 72 mol% SiO2, or any and all subranges formed by any of these endpoints.

[0090] The SiO2 concentration should be sufficiently high (greater than 55 mol%) to form a penelope crystalline phase when the precursor glass is heat-treated to transform into a glass-ceramic. In other words, the SiO2 concentration should be sufficiently high to obtain both lithium silicate and penelope phases. The amount of SiO2 can be limited to control the melting temperature (200 poise), because the melting temperature of pure SiO2 or high-SiO2 glasses is undesirably high.

[0091] Similar to SiO2, Al2O3 can also provide stability to the network and offers improved mechanical properties and chemical durability. However, if the amount of Al2O3 is too high, the fraction of lithium silicate crystals may decrease, potentially to the point where interlocking structures cannot be formed. The amount of Al2O3 can be tailored to control viscosity. Furthermore, if the amount of Al2O3 is too high, the viscosity of the melt generally also increases. In some embodiments, the glass or glass-ceramic composition may contain 0 to 6 mol% Al2O3. In some embodiments, the glass or glass-ceramic composition may comprise 0 to 6 mol%, 0 to 5 mol%, 0 to 4 mol%, 0 to 3 mol%, 0 to 2 mol%, 0 to 1 mol%, greater than 0 to 6 mol%, greater than 0 to 5 mol%, greater than 0 to 4 mol%, greater than 0 to 3 mol%, greater than 0 to 2 mol%, greater than 0 to 1 mol%, 0.5 to 6 mol%, 0.5 to 5 mol%, 0.5 to 4 mol%, 0.5 to 3 mol%, 0.5 to 2 mol%, 0.5 to 1 mol%, 1 to 6 mol%, 1 to 5 mol%, 1 to 4 mol%, 1 to 3 mol%, 1 to 2 mol%, 2 to 6 mol%, 2 to 5 mol%, 2 to 4 mol%, 2 to 3 mol%, 3 to 6 mol%, 3 to 5 mol%, 3 to 4 mol%, 4 to 6 mol%, 4 to 5 mol%, or 5 to 6 mol% Al2O3, or any and all subranges formed by any of these endpoints.

[0092] In the glasses and glass-ceramics described herein, Li₂O facilitates the formation of both the pyrite and lithium silicate crystalline phases. To obtain pyrite and lithium silicate as the main crystalline phases, a concentration of 14 mol% or more of Li₂O in the composition is desirable. However, if the concentration of Li₂O is too high—greater than 36 mol%—the composition becomes extremely flowable, and the feed viscosity is too low to form sheets. In some specific embodiments, the glass or glass-ceramic may contain 20 mol% to 32 mol% of Li₂O. In some embodiments, the glass or glass-ceramic composition may comprise 20 to 32 mol%, 20 to 30 mol%, 20 to 28 mol%, 20 to 26 mol%, 20 to 24 mol%, 22 to 32 mol%, 22 to 30 mol%, 22 to 28 mol%, 22 to 26 mol%, 22 to 24 mol%, 24 to 32 mol%, 24 to 30 mol%, 24 to 28 mol%, 24 to 26 mol%, 26 to 32 mol%, 26 to 30 mol%, 26 to 28 mol%, 28 to 32 mol%, 28 to 30 mol%, or 30 to 32 mol% of Li₂O, or any and all subranges formed by any of these endpoints.

[0093] As mentioned above, Li₂O is generally used to form glass-ceramics in specific embodiments, but other alkali metal oxides (such as K₂O and Na₂O) tend to reduce glass-ceramic formation and form aluminosilicate residual glass rather than a ceramic phase in the glass-ceramic. It has been found that Na₂O or K₂O or combinations thereof exceeding 10 mol% results in an amount of undesirable residual glass, which, from a mechanical perspective, can lead to deformation and undesirable microstructures during crystallization. Furthermore, Na₂O levels greater than 10 mol% can make the surface susceptible to subsurface hydration, which can lead to the growth of sodium carbonate crystals on the surface. These sodium carbonate crystals can then produce surface haziness on the glass-ceramic. However, levels below 5 mol% may be advantageous for ion exchange, resulting in higher surface compression and / or stoichiometry. Generally, the compositions described herein have low amounts of non-lithium alkali metal oxides. In some embodiments, the glass or glass-ceramic composition may contain 0 to 5 mol% R₂O, wherein R is one or more of the alkali metal cations Na and K. In some embodiments, the glass or glass-ceramic composition may contain 1 to 4 mol% of R₂O, wherein R is one or more of the alkali metal cations Na and K. In some embodiments, the glass or glass-ceramic composition may contain 0 to 5 mol%, 0 to 4 mol%, 0 to 3 mol%, 0 to 2 mol%, 0 to 1 mol%, >0 to 5 mol%, >0 to 4 mol%, >0 to 3 mol%, >0 to 2 mol%, >0 to 1 mol%, 1 to 5 mol%, 1 to 4 mol%, 1 to 3 mol%, 1 to 2 mol%, 2 to 5 mol%, 2 to 4 mol%, 2 to 3 mol%, 3 to 5 mol%, 3 to 4 mol%, or 4 to 5 mol% of Na₂O or K₂O, or combinations thereof. It should be understood that the R₂O concentration may be within a subrange formed by any and all of the foregoing endpoints.

[0094] Glass and glass-ceramic compositions may contain P2O5. P2O5 can be used as a nucleating agent to produce bulk nucleation of the crystalline phase from the glass and glass-ceramic compositions. If the concentration of P2O5 is too low, the precursor glass crystallizes, but only at higher temperatures (due to lower viscosity); however, if the concentration of P2O5 is too high, crystallization may be difficult to control after cooling during precursor glass formation. Embodiments may contain >0 to 3 mol% P2O5. Other embodiments may contain >0.7 to 2.2 mol% P2O5. The specific composition may contain >0 to 3 mol%, >0 to 2.5 mol%, >0 to 2.2 mol%, >0 to 2 mol%, >0 to 1.5 mol%, >0 to 1.2 mol%, >0 to 1 mol%, 0.7 to 3 mol%, 0.7 to 2.5 mol%, 0.7 to 2.2 mol%, 0.7 to 2 mol%, 0.7 to 1.5 mol%, 0.7 to 1.2 mol%, 0.7 to 1 mol%, 1 to 3 mol%, 1 to 2.5 mol%, 1 to 2.2 mol%, 1 to 2 mol%, 1 to 1.5 mol%, 1 to 1.2 mol%, 1.2 to 3 mol%, 1.2 to 2.5 mol%, 1.2 to 2.2 mol%, 1.2 to 2 mol%, 1.5 to 3 mol%, 1.5 to 2.5 mol%, 1.5 to 2 mol%, 2 to 3 mol%, 2 to 2.5 mol%, 2.2 to 3 mol%, 2.5 to 3 mol% of P2O5, or any and all subranges formed by any of these endpoints.

[0095] In the glasses and glass-ceramics described herein, the addition of ZrO2 improves the stability of Li2O-Al2O3-SiO2-P2O5 glasses by significantly reducing glass crystallization during forming and lowering the liquidus temperature. At concentrations greater than 4 mol%, ZrO2 can form the main liquidus phase at high temperatures, which significantly reduces the liquidus viscosity. When the glass contains more than 1 mol% ZrO2, transparent glasses can be formed. The addition of ZrO2 also reduces the grain size of the lepidolite, which contributes to the formation of transparent glass-ceramics. In some embodiments, the glass or glass-ceramic composition may contain 1.7 to 4.5 mol% ZrO2. In some embodiments, the glass or glass-ceramic composition may contain 2 to 4 mol% ZrO2. In some embodiments, the glass or glass-ceramic composition may comprise 1.7 to 4.5 mol%, 1.7 to 4 mol%, 1.7 to 3.5 mol%, 1.7 to 3 mol%, 1.7 to 2.5 mol%, 1.7 to 2 mol%, 2 to 4.5 mol%, 2 to 4 mol%, 2 to 3.5 mol%, 2 to 3 mol%, 2 to 2.5 mol%, 2.5 to 4.5 mol%, 2.5 to 4 mol%, 2.5 to 3.5 mol%, 2.5 to 3 mol%, 3 to 4.5 mol%, 3 to 4.5 mol%, 3 to 4.5 mol%, 3 to 3.5 mol%, 3.5 to 4.5 mol%, 3.5 to 4.5 mol%, 4 to 4.5 mol% of ZrO2, or any and all subranges formed by any of these endpoints.

[0096] B₂O₃ lowers the melting temperature of the glass precursor. Furthermore, the addition of B₂O₃ to the precursor glass, and consequently to the glass-ceramic, contributes to an interlocking crystal microstructure and improves the damage resistance of the glass-ceramic. When boron in the residual glass is not charged-balanced by alkali metal oxides or divalent cation oxides (e.g., MgO, CaO, SrO, BaO, and ZnO), it will be in a tricoordinate state (or tricoordinate boron), opening the glass structure. The network around these tricoordinate boron atoms is not as rigid as that of tetrahedral (or tetracoordinate) boron. Theoretically, it is thought that precursor glasses and glass-ceramics containing tricoordinate boron allow for some degree of deformation before crack initiation compared to tetracoordinate boron. This allowance of deformation increases the Vickers indentation crack initiation threshold. The fracture toughness of precursor glasses and glass-ceramics containing tricoordinate boron can also be increased. Beyond theoretical considerations, it is believed that the presence of boron in the residual glass (and precursor glass) of glass-ceramics reduces the viscosity of the residual glass (or precursor glass), which promotes the growth of lithium silicate crystals, especially large crystals with high aspect ratios. A greater amount of tricoordinated boron (as opposed to tetracoordinated boron) is thought to result in glass-ceramics exhibiting greater Vickers indentation crack initiation loads. In some embodiments, the amount of tricoordinated boron (as a percentage of total B₂O₃) can be 40% or more, 50% or more, 75% or more, 85% or more, or even 95% or more. Generally, the amount of boron needs to be controlled to maintain the chemical durability and mechanical strength of the ceramized bulk glass-ceramic. In other words, the amount of boron should be limited to less than 5 mol% to maintain chemical durability and mechanical strength.

[0097] In one or more embodiments, the glass and glass-ceramic of this document may contain 0 to 2 mol% of B2O3. In some embodiments, the glass or glass-ceramic composition may contain 0 to 2 mol%, 0 to 1.5 mol%, 0 to 1 mol%, 0 to 0.5 mol%, >0 to 2 mol%, >0 to 1.5 mol%, >0 to 1 mol%, >0 to 0.5 mol%, 0.5 to 2 mol%, 0.5 to 1.5 mol%, 0.5 to 1 mol%, 1 to 2 mol%, 1 to 1.5 mol%, 1.5 to 2 mol% of B2O3, or any and all subranges formed by any of these endpoints.

[0098] MgO can be incorporated into the lepidolite crystals in the form of a partial solid solution. In one or more embodiments, the glass and glass-ceramic described herein may contain 0 to 1 mol%, 0 to 0.75 mol%, 0 to 0.5 mol%, 0 to 0.25 mol%, >0 to 1 mol%, >0 to 0.75 mol%, >0 to 0.5 mol%, >0 to 0.25 mol%, 0.25 to 1 mol%, 0.25 to 0.75 mol%, 0.25 to 0.5 mol%, 0.5 to 1 mol%, 0.5 to 0.75 mol%, 0.75 to 1 mol% of MgO, or any and all subranges formed by any of these endpoints.

[0099] ZnO can be incorporated into the lithopsid crystal in the form of a partial solid solution. In one or more embodiments, the glass and glass-ceramic described herein may contain 0 to 1 mol% ZnO. In one or more embodiments, the glass and glass-ceramic described herein may contain 0 to 1 mol%, 0 to 0.75 mol%, 0 to 0.5 mol%, 0 to 0.25 mol%, >0 to 1 mol%, >0 to 0.75 mol%, >0 to 0.5 mol%, >0 to 0.25 mol%, 0.25 to 1 mol%, 0.25 to 0.75 mol%, 0.25 to 0.5 mol%, 0.5 to 1 mol%, 0.5 to 0.75 mol%, 0.75 to 1 mol% ZnO, or any and all subranges formed by any of these endpoints.

[0100] In one or more embodiments, the glass and glass-ceramic may contain 0 to 0.5 mol% of SnO2 or another clarifying agent. In some embodiments, the glass or glass-ceramic composition may contain 0 to 0.5 mol%, 0 to 0.4 mol%, 0 to 0.3 mol%, 0 to 0.2 mol%, 0 to 0.1 mol%, 0.05 to 0.5 mol%, 0.05 to 0.4 mol%, 0.05 to 0.3 mol%, 0.05 to 0.2 mol%, 0.05 to 0.1 mol%, 0.1 to 0.5 mol%, 0.1 to 0.4 mol%, 0.1 to 0.3 mol%, 0.1 to 0.2 mol%, 0.2 to 0.5 mol%, 0.2 to 0.4 mol%, 0.2 to 0.3 mol%, 0.3 to 0.5 mol%, 0.3 to 0.4 mol%, or 0.4 to 0.5 mol% of SnO2, or any and all subranges formed by any of these endpoints.

[0101] Due to the raw materials and / or equipment used to produce the glass or glass-ceramic compositions of various embodiments, certain impurities or components may be unintentionally added to the final glass or glass-ceramic composition. These materials may be present in small amounts in the glass or glass-ceramic composition and are referred to herein as "inclusion materials." As used herein, "inclusion materials" may be present in amounts less than 1000 ppm. In some embodiments, the glass or glass-ceramic composition may further comprise inclusion materials, such as TiO2, MnO, ZnO, Nb2O5, MoO3, Ta2O5, WO3, Y2O3, La2O3, HfO2, CdO, As2O3, Sb2O3, sulfur-based compounds (e.g., sulfates), halogens, or combinations thereof. In some embodiments, the glass or glass-ceramic composition may comprise antimicrobial components, chemical clarifying agents, or other additional components.

[0102] In some embodiments, the glass and / or glass-ceramics described herein can be manufactured into sheets by processes including but not limited to fusion forming, slot drawing, float glass, rolling, and other sheet forming processes known to those skilled in the art.

[0103] Articles formed from the glass-ceramics described herein can have any suitable thickness, which may vary depending on the specific application using the glass-ceramics. Glass sheets and / or glass-ceramic embodiments may have a thickness from 0.4 mm to 10 mm. Some embodiments may have a thickness less than or equal to 6 mm, less than or equal to 5 mm, less than or equal to 3 mm, less than or equal to 2 mm, less than or equal to 1.0 mm, less than or equal to 750 µm, less than or equal to 500 µm, or less than or equal to 250 µm. Some glass or glass-ceramic sheet embodiments may have a thickness of 200 µm to 5 mm, 500 µm to 5 mm, 200 µm to 4 mm, 200 µm to 2 mm, 400 µm to 5 mm, or 400 µm to 2 mm. The thickness of some glass or glass-ceramic sheet embodiments can be 250 µm to 5 mm, 400 µm to 4 mm, 350 µm to 3 mm, 450 µm to 2 mm, 500 µm to 1 mm, or 550 µm to 750 µm. In some embodiments, the thickness can be 3 mm to 6 mm, or 0.8 mm to 3 mm. It should be understood that the article thickness can be within a subrange formed by any and all of the aforementioned endpoints.

[0104] In the various embodiments described herein, the glass ceramic is chemically strengthened, for example by ion exchange treatment, to improve the chemical durability and damage resistance of the glass ceramic, while enabling metrological measurements and preventing the formation of a fog layer under high humidity conditions.

[0105] When the glass-ceramics described herein undergo conventional ion exchange treatment (e.g., ion exchange treatment with molten sodium nitrate, potassium nitrate, or a mixture of sodium nitrate / potassium nitrate salts), the resulting glass-ceramics exhibit high stored energy and a maximum central tensile strength of approximately 70 MPa to approximately 140 MPa. These glass articles also exhibit high fracture toughness (K0 measured according to the standard V-notch test). 1C It is 1.1 MPa√m, or K is measured according to the double cantilever beam (DCB) method. 1C 1.32 MPa m 1 / 2 Furthermore, it is non-brittle at a thickness of 0.8 mm, while the glass within it would be brittle. These glass-ceramics can also exhibit the desired mechanical properties.

[0106] However, the crystalline phases of these glass-ceramics may also undergo ion exchange during ion exchange treatment. For example, when lithium in the lithium pyrosilicate crystalline phase exchanges with sodium in the ion exchange bath, this can form a highly sodium-rich, low-refractive-index surface layer (i.e., a layer with a refractive index lower than that of the glass-ceramic product), such as... Figure 1 As shown. Specifically, ion exchange between lithium pyrosilicate and sodium ions can yield low-refractive-index silicates added to the glass phase of glass ceramics, as well as the formation of sodium silicate and sodium disilicate within the surface layer. Figure 1 This is a graph showing the distribution of sodium, lithium, and potassium in a glass-ceramic article having composition A in Table 1 after ion exchange in a mixed KNO3 / NaNO3 salt containing less than 0.04 wt% LiNO3. To produce the glass-ceramic article of composition A (as in the sample having composition A used below), the article was heated at 570°C for 4 hours, then at 740°C for 1 hour, followed by typical cooling of the glass-ceramic article. After the aforementioned ceramization cycle, the article had 9 to 15 wt% residual glass phase, 40-48 wt% lithium pyrosilicate crystalline phase, 39-45 wt% lithopone crystalline phase, and less than about 3 wt% lithium metasilicate crystalline phase, wherein each crystalline phase was measured by X-ray diffraction, and the standard deviation of the main phase was about 1.2 wt%.

[0107] Table 1:

[0108] like Figure 1 As shown, the surface layer is rich in sodium, in which sodium undergoes ion exchange with lithium ions, and both the glass and the crystalline phase undergo ion exchange.

[0109] Figure 2A and 2B This is an FSM image taken at a wavelength of 365 nm. (Example) Figure 2AAs shown, because the refractive index of the surface layer is lower than that of the glass-ceramic product, the FSM image of the product is blurry, which makes it unreliable to use FSM as a quality control method to monitor the ion exchange process, especially when the thickness of the ion exchange layer is less than about 3 µm.

[0110] Furthermore, the extremely low levels of lithium poisoning in the salt bath prevented the formation of a high-stress layer resulting from ion exchange between sodium ions and lithium in lithium pyrosilicate. In other words, 0.04 wt% LiNO3 in the ion exchange bath was sufficient to prevent the formation of streaks, as... Figure 2B As shown. To prevent lithium poisoning, approximately 0.01 m³ of ion exchange is performed per 1 kg of salt. 2 After the glass ceramics are removed, the salt in the tank needs to be replaced.

[0111] Furthermore, this sodium-rich surface layer makes the glass-ceramic surface susceptible to subsurface hydration, which can lead to the growth of sodium carbonate crystals on the surface, resulting in a hazy surface, such as... Figure 3 As shown. Figure 3 It has Figure 1 Optical micrographs of glass artifacts with elemental distribution obtained after exposure to 85 °C and 85% relative humidity for 48 hours. Figure 3 The dendritic growth shown is sodium carbonate crystals. More specifically, sodium carbonate crystal growth occurs when hydrated hydrogen ions from water exchange with sodium ions and migrate into the glass subsurface layer, the sodium ions emerge from the glass surface, and over time, Na₂CO₃ is formed on the glass through the reaction of sodium ions with atmospheric CO₂. This sodium carbonate growth can occur when atmospheric moisture is present on the glass for a prolonged period, for example, when parts are packaged in a high-humidity environment and atmospheric moisture is trapped between the glass surface and the packaging film.

[0112] The formation of a sodium-rich surface layer also makes the surface susceptible to preferential etching and pitting during polishing and washing, such as... Figure 4A and 4B shown. Specifically, Figure 4A and 4B This is an atomic force microscope (AFM) image of a 500 nm x 500 nm sample after ion exchange, polishing, and washing. Figure 4A The surface roughness of a glass article formed from a glass composition having the following nominal composition and subjected to ion exchange according to a conventional ion exchange treatment as described in Example A is depicted, wherein the nominal composition, in mole % is 71 SiO2; 1.9 B2O3; 12.8 Al2O3; 2.4 Na2O; 8.2 Li2O; 2.9 MgO; 0.8 ZnO; 0.02 Fe2O3; 0.01 ZrO2; 0.06 SnO2. Figure 4BThe surface roughness of a glass-ceramic formed from composition A and subjected to ion exchange in a mixed KNO3 / NaNO3 salt containing less than 0.04 wt% LiNO3 is described. Polishing and washing can result in high surface roughness due to the low chemical durability of the sodium-rich surface layer, which reduces the durability of coatings suitable for cover glass applications. These coatings, for example but not limited to, can provide cover glass with scratch resistance, anti-reflective properties, oleophobic or hydrophobic properties.

[0113] In the various embodiments described herein, the glass-ceramic is chemically strengthened through ion exchange treatment to improve its chemical durability and damage resistance, while also enabling metrological measurements and preventing the formation of a haze layer under high humidity conditions. Embodiments of the ion exchange treatment will now be described in more detail.

[0114] Single-stripe ion exchange treatment In various embodiments, ion exchange treatment of the glass-ceramic article yields a waveguide layer that produces a fringe in each polarization state in FSM measurements, referred to herein as a "single-fringe IOX". In these embodiments, the sodium-to-lithium ion exchange rate is such that the decrease in refractive index of the surface layer is less than the rate at which the refractive index increases due to potassium-to-sodium ion exchange in the surface layer, thereby allowing the formation of the waveguide layer.

[0115] In various embodiments, the single-strip IOX treatment includes applying an ion-exchange medium to one or more surfaces of a glass-ceramic article. The ion-exchange medium may be a molten salt bath, solution, paste, gel, or another suitable medium comprising KNO3, NaNO3, and LiNO3.

[0116] In various embodiments, based on the total amount of NaNO3 and KNO3 in the ion exchange medium, the ion exchange medium contains greater than 0 wt% NaNO3 and less than or equal to about 20 wt% NaNO3. For example, based on the total amount of NaNO3 and KNO3 in the ion exchange medium, the ion exchange medium in various embodiments may contain >0 wt% to 20 wt%, >0 wt% to 15 wt%, >0 wt% to 12 wt%, >0 wt% to 10 wt%, >0 wt% to 7.5 wt%, >0 wt% to 5 wt%, 2.5 wt% to 20 wt%, 2.5 wt% to 15 wt%, 2.5 wt% to 12 wt%, 2.5 wt% to 10 wt%, 2.5 wt% to 7.5 wt%, 2.5 wt% to 20 wt%, 2.5 wt% to 15 wt%, 2.5 wt% to 12 wt%, 2.5 wt% to 10 wt%, 2.5 wt% to 7.5 wt%, 2.5 NaNO3, or any and all subranges formed by any of these endpoints, in weight percentages of 5% to 5%, 5% to 20%, 5% to 15%, 5% to 12%, 5% to 10%, 5% to 7.5%, 7.5% to 20%, 7.5% to 15%, 7.5% to 12%, 7.5% to 10%, 10% to 20%, 10% to 15%, 10% to 12%.

[0117] In various embodiments, the ion exchange medium contains approximately 80% to less than 100% by weight of KNO3, based on the total amount of NaNO3 and KNO3 in the ion exchange medium. For example, based on the total amount of NaNO3 and KNO3 in the ion exchange medium, the ion exchange medium of various embodiments may contain 80 wt% to 99.9 wt%, 80 wt% to 97.5 wt%, 80 wt% to 95 wt%, 80 wt% to 92.5 wt%, 80 wt% to 90 wt%, 90 wt% to 99.9 wt%, 90 wt% to 97.5 wt%, 90 wt% to 95 wt%, 90 wt% to 92.5 wt%, 92.5 wt% to 99.9 wt%, 92.5 wt% to 97.5 wt%, 92.5 wt% to 95 wt%, 95 wt% to 99.9 wt%, 95 wt% to 97.5 wt%, 97.5 wt% to 99.9 wt% of KNO3, or any and all subranges formed by any of these endpoints.

[0118] According to various embodiments, the ion exchange medium further comprises 0.01 wt% to 0.5 wt% LiNO3 based on the total weight of the salt in the ion exchange medium. For example, the ion exchange medium of various embodiments may comprise 0.01 wt% to 0.5 wt%, 0.01 wt% to 0.3 wt%, 0.01 wt% to 0.1 wt%, 0.1 wt% to 0.5 wt%, 0.1 wt% to 0.3 wt%, 0.3 wt% to 0.5 wt% LiNO3, or any and all subranges formed by any of these endpoints. In some specific embodiments, the ion exchange medium comprises 0.1 wt%, 0.09 wt%, 0.08 wt%, 0.07 wt%, or 0.06 wt% LiNO3 based on the total weight of the salt in the ion exchange medium.

[0119] The ion exchange treatment can be a single-step or multi-step process, for example, a two-step or three-step process. In embodiments where the ion exchange treatment includes multiple steps, it should be understood that each step includes applying an ion exchange medium to the glass-ceramic article, and the ion exchange medium for each step may differ from the ion exchange medium for one or more other steps. However, each ion exchange medium contains greater than 0 wt% and less than or equal to about 20 wt% of NaNO3 based on the total amount of NaNO3 and KNO3 in the ion exchange medium, about 80 wt% to less than 100 wt% of KNO3 based on the total amount of NaNO3 and KNO3 in the ion exchange medium, and 0.01 wt% to 0.5 wt% of LiNO3 based on the total weight of the salt in the ion exchange medium.

[0120] In various embodiments, the temperature of the molten salt bath can be from about 380 °C to about 550 °C, and the immersion time can be from about 2 hours to about 16 hours.

[0121] Stripe-free ion exchange treatment In various embodiments, the ion exchange treatment uses a lower potassium concentration than is effectively used to generate surface waveguides for FSM measurements, referred to herein as “stripeless IOX”. In these embodiments, the potassium, sodium, and lithium concentrations in the ion exchange medium are adapted to limit the average sodium oxide content from the surface to a depth of 100 nm from the glass-ceramic article to less than 10 mol% sodium oxide, as measured using glow discharge photoemission spectroscopy (GDOES). Although lacking surface waveguides, the surface layer in these embodiments exhibits chemical durability, making it particularly suitable for cover glass applications.

[0122] In various embodiments, the stripe-free IOX treatment includes applying an ion-exchange medium to one or more surfaces of a glass-ceramic article. The ion-exchange medium may be a solution, paste, gel, or another suitable medium comprising KNO3, NaNO3, and LiNO3.

[0123] In various embodiments, based on the total amount of NaNO3 and KNO3 in the ion exchange medium, the ion exchange medium contains greater than 20 wt% NaNO3 and less than or equal to about 50 wt% NaNO3. For example, based on the total amount of NaNO3 and KNO3 in the ion exchange medium, the ion exchange medium of various embodiments may contain 20 wt% to 50 wt%, 20 wt% to 45 wt%, 20 wt% to 40 wt%, 20 wt% to 35 wt%, 20 wt% to 30 wt%, 30 wt% to 50 wt%, 30 wt% to 45 wt%, 30 wt% to 40 wt%, 30 wt% to 35 wt%, 35 wt% to 50 wt%, 35 wt% to 45 wt%, 35 wt% to 40 wt%, 40 wt% to 50 wt%, 40 wt% to 45 wt%, 45 wt% to 50 wt% NaNO3, or any and all subranges formed by any of these endpoints. However, it should be understood that in some implementations, NaNO3 may be included in an amount greater than 50% by weight, but in such cases, depending on the specific amount of NaNO3 and the temperature of the ion exchange treatment, an amount of LiNO3 greater than about 0.15% by weight may be beneficial.

[0124] In various embodiments, the ion exchange medium contains approximately 50 wt% to approximately 80 wt% of KNO3, based on the total amount of NaNO3 and KNO3 in the ion exchange medium. For example, based on the total amount of NaNO3 and KNO3 in the ion exchange medium, the ion exchange medium of various embodiments may contain 50 wt% to 80 wt%, 50 wt% to 70 wt%, 50 wt% to 65 wt%, 50 wt% to 60 wt%, 50 wt% to 55 wt%, 55 wt% to 80 wt%, 55 wt% to 70 wt%, 55 wt% to 65 wt%, 55 wt% to 60 wt%, 55 wt% to 60 wt%, 60 wt% to 70 wt%, 60 wt% to 65 wt%, 65 wt% to 80 wt%, 65 wt% to 70 wt%, 70 wt% to 80 wt% of KNO3, or any and all subranges formed by any of these endpoints.

[0125] According to various embodiments, the ion exchange medium further comprises 0.04 wt% to 0.5 wt% LiNO3 based on the total weight of the salt in the ion exchange medium. For example, based on the total weight of the salt in the ion exchange medium, the ion exchange medium of various embodiments may comprise 0.04 wt% to 0.5 wt%, 0.04 wt% to 0.3 wt%, 0.04 wt% to 0.1 wt%, 0.1 wt% to 0.5 wt%, 0.1 wt% to 0.3 wt%, 0.3 wt% to 0.5 wt%, or any and all subranges formed by any of these endpoints. In some specific embodiments, based on the total weight of the salt in the ion exchange medium, the ion exchange medium comprises 0.1 wt%, 0.09 wt%, 0.08 wt%, 0.07 wt%, or 0.06 wt% LiNO3.

[0126] The ion exchange treatment can be a single-step or multi-step process, for example, a two-step or three-step process. In embodiments where the ion exchange treatment includes multiple steps, it should be understood that each step includes applying an ion exchange medium to the glass-ceramic article, and the ion exchange medium for each step may differ from the ion exchange medium for one or more other steps. However, each ion exchange medium contains greater than 20 wt% and less than or equal to about 50 wt% of NaNO3 based on the total amount of NaNO3 and KNO3 in the ion exchange medium, about 50 wt% to about 80 wt% of KNO3 based on the total amount of NaNO3 and KNO3 in the ion exchange medium, and 0.04 wt% to 0.5 wt% of LiNO3 based on the total weight of the salt in the ion exchange medium.

[0127] In various embodiments, the temperature of the molten salt bath can be from about 380 °C to about 550 °C, and the immersion time can be from about 2 hours to about 16 hours.

[0128] Not confined to theory, it is believed that in glass-ceramics formed from lithium pyrosilicate and / or the lepidolite family, when the concentration of NaNO3 in the ion exchange treatment exceeds approximately 20% by weight, the increase in refractive index due to potassium ion exchange is suppressed by the decrease in refractive index due to sodium exchange of lithium ions. Therefore, during streak-free ion exchange treatment, potassium streaks, typically suitable for FSM metrology, are not produced. For example, as... Figure 5 As shown, it provides the 365 nm FSM spectrum of a glass of composition A, which undergoes ion exchange in 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3. By comparison... Figure 5 and Figure 2A It can be seen in Figure 5 It did not appear in the middle. Figure 2AThe faint, low-refractive-index fringes observed indicate ion exchange between sodium and lithium in the crystalline phase. Therefore, FSM metrology may not be suitable for monitoring sodium ion exchange processes in stripeless IOX treatments.

[0129] However, surface compressive stress can be obtained from birefringence using FSM plots. For example, compression depth and central tension were obtained using an Orihara SLP 2000 scattering light photoelastic stressmeter operating at 405 nm, and the results are shown in... Figure 6 For transparent glass-ceramics, a wavelength of 405 nm can be particularly advantageous because it is believed to minimize speckle. However, higher wavelengths (e.g., 633 nm) can also be used, but these may significantly increase speckle. In some such embodiments, speckle can be averaged by moving the sample during measurement.

[0130] The Orihara SLP 2000 includes a built-in 2x magnification telecentric lens, which enables the camera to have a field of view of 600 µm in the depth direction. However, due to the high refractive index properties of glass-ceramics, the depth perception can extend to approximately 800 µm, thus enabling the use of the SLP 2000 to obtain complete stress distribution curve measurements of the various glass-ceramic articles described herein.

[0131] During operation, a 405 nm laser diode is periodically phase-modulated via a liquid crystal variable retarder before entering the glass ceramic. Due to the stress distribution in the glass ceramic, the scattered light undergoes changes in intensity and phase as it propagates through the thickness of the glass ceramic. As the light scatters in all directions, a camera positioned at 45° relative to the surface of the glass ceramic captures the vertical components of the intensity fluctuations along the laser path. The phase shift experienced at each point along the laser path is captured by image analysis, and the internal stress σ can be inferred from the following equation (2): (2) Where λ is the wavelength of the laser and β is the stress optical coefficient (SOC). It is the phase shift, and x is the optical path length.

[0132] The SLP 2000 software provides real-time visualization of the laser beam inside the sample. In various implementations, a sixth-order polynomial fit can be used to provide consistent results across a wide range of glass-ceramic samples. However, the processing area, laser wavelength, and appropriate fitting function can be varied depending on the specific implementation.

[0133] Alternatively, quality control measurements can be derived from the integral of compressive stress. Specifically, the integral of compressive stress from ion exchange is related to the number of ions exchanged. As larger ions replace smaller ions, the glass exhibits dimensional growth, which is related to center tension, as long as the ion exchange process is conducted below the peak center tension. Once the peak center tension is reached, although growth still occurs during ion exchange, the correlation between dimensional growth and center tension no longer holds true. Figure 7 An example of the correlation between % size growth and center tension is shown for three different salt concentrations.

[0134] exist Figure 7 In the figure, the central tension (in MPa) is shown along the X-axis, while the dimensional increase in length (in %) is shown along the Y-axis. Each glass-ceramic sample was made from composition A. Curve 702 shows the correlation of glass-ceramic samples undergoing ion exchange at 470 °C in a bath containing 50 wt% KNO3, 50 wt% NaNO3, and 0.1 wt% LiNO3. Curve 704 shows the correlation of glass-ceramic samples undergoing ion exchange at 470 °C in a bath containing 70 wt% KNO3, 30 wt% NaNO3, and 0.1 wt% LiNO3. Curve 706 shows the correlation of glass-ceramic samples undergoing ion exchange at 500 °C in a bath containing 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3. Figure 7 As shown, the % size growth from ion exchange can be used as a method to measure compressive stress below the peak compressive stress value. Specifically, curve 706 shows that after 8 hours, the central tension reaches approximately 95 MPa, and the increased ion exchange shows that the increase in size growth is not related to the compressive stress. Specifically, for transparent glass and glass-ceramic materials, the size growth can be related to the central tension according to the following equation (3): (3) Where CT is the center tension (in MPa) and DG is the length increase when the center tension is lower than the peak center tension.

[0135] For opaque materials, the % size growth can be calibrated using the elemental distribution obtained by a microprobe, and converted into stress using the lattice dilation constant according to the following equation (4): (4) Where C(z) is the concentration of the large cation at z, h is the glass thickness, B is the network expansion coefficient, E is Young's modulus, v is Poisson's ratio, and z is the distance from the glass surface along the glass thickness, which is 0 and h at the surface.

[0136] Ion exchange glass ceramic products In various embodiments, the resulting ion-exchange glass-ceramic article can be transparent or opaque, and the depth of compression (DOC) extends approximately 0.18 meters from the outer surface of the ion-exchange glass-ceramic article. t To approximately 0.25 t ,in, t This refers to the thickness of the ion-exchange glass-ceramic product. In other words, the stress in the ion-exchange glass-ceramic product is located at a distance of approximately 0.18 meters from the outer surface of the product. t To approximately 0.25 t At a depth of [insert depth here], the stress transitions from compressive to tensile. In various embodiments, the depth of compression (DOC) can be greater than 80 µm. For example, the compression depth can be 80 µm to 300 µm, 100 µm to 250 µm, 150 µm to 200 µm, or any and all subranges formed by any of these endpoints. A deep DOC can provide resistance to damage, for example, resistance to sharp defects that can occur when a glass-ceramic article is dropped onto a rough surface (such as bitumen).

[0137] In the various embodiments described herein, the maximum compressive stress (absolute value) at the outer surface of the resulting ion-exchange glass-ceramic article is 1.8 to 2.2 times the maximum central tension (absolute value) (CT) of the ion-exchange glass-ceramic article. For example, the absolute value of the maximum compressive stress may be, for example, 2|CT|. In the embodiments, the absolute value of the maximum central tension is at least 60 MPa or greater, or 70 MPa or greater. For example, the absolute value of the maximum center tension can be 60 MPa to 160 MPa, 60 MPa to 150 MPa, 60 MPa to 140 MPa, 60 MPa to 130 MPa, 60 MPa to 120 MPa, 60 MPa to 110 MPa, 60 MPa to 100 MPa, 70 MPa to 160 MPa, 70 MPa to 150 MPa, 70 MPa to 140 MPa, 70 MPa to 130 MPa, 70 MPa to 120 MPa, 70 MPa to 110 MPa, 70 MPa to 100 MPa, 80 MPa to 160 MPa, 80 MPa to 150 MPa, 80 MPa to 140 MPa, 80 MPa to 130 MPa, 80 MPa to 120 MPa, 80 MPa to 110 MPa, 80 MPa to 100 MPa, 90 MPa... MPa to 160 MPa, 90 MPa to 150 MPa, 90 MPa to 140 MPa, 90 MPa to 130 MPa, 90 MPa to 120 MPa, 90 MPa to 110 MPa, 90 MPa to 100 MPa, 100 MPa to 160 MPa, 100 MPa to 150 MPa, 100 MPa to 140 MPa, 100 MPa to 130 MPa, 100 MPa to 120 MPa, 100 MPa to 110 MPa, or any and all subranges formed by any of these endpoints.

[0138] In various embodiments, the ion-exchange glass-ceramic articles also have a maximum compressive stress of 108 MPa to 350 MPa. For example, the absolute value of the maximum compressive stress can be 108 MPa to 350 MPa, 108 MPa to 325 MPa, 108 MPa to 300 MPa, 108 MPa to 275 MPa, 108 MPa to 250 MPa, 108 MPa to 225 MPa, 108 MPa to 200 MPa, 180 MPa to 350 MPa, 180 MPa to 325 MPa, 180 MPa to 300 MPa, 180 MPa to 275 MPa, 180 MPa to 250 MPa, 180 MPa to 225 MPa, 180 MPa to 200 MPa, 200 MPa to 350 MPa, 200 MPa to 325 MPa, 200 MPa to 300 MPa, 200 MPa to 275 MPa, 200 MPa to 250 MPa, 200 MPa to 225 MPa. MPa, 225 MPa to 350 MPa, 225 MPa to 325 MPa, 225 MPa to 300 MPa, 225 MPa to 275 MPa, 225 MPa to 250 MPa, 250 MPa to 350 MPa, 250 MPa to 325 MPa, 250 MPa to 300 MPa, 250 MPa to 275 MPa, 275 MPa to 350 MPa, 275 MPa to 325 MPa, 275 MPa to 300 MPa, 300 MPa to 350 MPa, 300 MPa to 325 MPa, 325 MPa to 350 MPa, or any and all subranges formed by any of these endpoints.

[0139] Fracture toughness can also be used to characterize ion-exchange glass-ceramic articles. In various embodiments, the fracture toughness of the ion-exchange glass-ceramic articles is 1 MPa√m or greater, which is measured according to the double cantilever beam method on samples having the same composition but not ion-exchanged. For example, in various embodiments, the fracture toughness of the ion-exchange glass-ceramic articles is from 1 MPa√m to 1.5 MPa√m, which is measured according to the double cantilever beam method.

[0140] The various embodiments described herein can also be used to reduce the fragility of glass-ceramic articles. Therefore, in each embodiment, the glass-ceramic article is not easily broken after ion exchange. Fragility property refers to the specific fracture behavior exhibited by a glass-ceramic article when subjected to impact or damage. As used herein, glass is considered non-fragile when it exhibits one or more of the following in the test area due to a fragility test: (1) four or fewer fragments with a maximum size of 1 mm or larger, and / or (2) the number of bifurcations is less than or equal to the number of crack branches. Fragments, bifurcations, and crack branches are calculated based on any 2-inch × 2-inch square centered on the impact point. Therefore, for any 2-inch × 2-inch square centered on the impact point, if the glass meets one or both of tests (1) and (2), the impact point being the location where breakage occurs according to the following procedure. In the fragility test, an impact probe is brought into contact with the glass, and the depth to which the impact probe penetrates into the glass increases with each successive contact. The progressively increasing depth of the impact probe ensures that the imperfections produced by the impact probe reach the tension zone, while preventing the application of excessive external force that could hinder accurate determination of the glass's brittleness properties. In some embodiments, the depth of the impact probe in the glass can be increased by approximately 5 µm with each repeated contact, wherein the impact probe does not contact the glass between each repeated contact. The test area is any 2-inch × 2-inch square centered on the impact point. As used herein, crack branches originate from the impact point, and if any portion of the fragment extends into the test area, the fragment is considered to be within the test area. While coatings, adhesive layers, etc., may be used in conjunction with the reinforced glass articles described herein, these external constraints are not used to determine the brittleness or brittleness properties of the glass-ceramic articles. In some embodiments, a film that does not affect the fracture properties of the glass-ceramic article may be applied to the glass-ceramic article prior to the brittleness test to prevent fragments from ejecting from the glass article, thereby improving the safety of personnel performing the test.

[0141] In contrast, fragile glass articles do not exhibit four or fewer fragments or a number of branches less than or equal to the number of crack branches. In the fragility test described herein, an impact is transmitted to the surface of the glass article by a force just sufficient to release the internal stored energy present in the glass article. That is, a point impact force is sufficient to create one or more new cracks on the surface of the tempered glass sheet and cause the cracks to extend through the compression zone (i.e., to the compression depth) into the tension zone (i.e., the area under central tension).

[0142] Therefore, the chemically strengthened glass-ceramic products described in this article are "non-fragile"—that is, they do not exhibit the brittle properties described above when subjected to impact from a sharp object.

[0143] Example To facilitate a better understanding of the various implementation methods, reference is made to the following examples, which are intended to illustrate the various implementation methods. Unless otherwise indicated, the thickness of each sample in each example is 0.8 mm.

[0144] Example 1 Glass-ceramic samples formed from composition A were subjected to different ion exchange treatments, and FSM spectra of each sample were obtained using 365 nm refractive FSM. The results are shown in... Figures 8A-8E .

[0145] exist Figure 8A In this process, glass-ceramic samples were subjected to ion exchange treatment at 500 °C for 10 hours in a bath containing 100 wt% KNO3 and 0.1 wt% LiNO3. Figure 8B In this process, glass-ceramic samples were subjected to ion exchange treatment at 500 °C for 12 hours in a bath containing 95 wt% KNO3, 5 wt% NaNO3, and 0.1 wt% LiNO3. Figure 8C In this process, glass-ceramic samples were subjected to ion exchange treatment at 500 °C for 12 hours in a bath containing 90 wt% KNO3, 10 wt% NaNO3, and 0.1 wt% LiNO3. Figures 8A-8C As shown, TE and TM stripes were generated for ion exchange quality control metrology.

[0146] exist Figure 8D In this process, glass-ceramic samples were subjected to ion exchange treatment at 500 °C for 16 hours in a bath containing 80 wt% KNO3, 20 wt% NaNO3, and 0.1 wt% LiNO3. Figure 8E In this process, glass-ceramic samples were subjected to ion exchange treatment at 480 °C for 16 hours in a bath containing 80 wt% KNO3, 20 wt% NaNO3, and 0.1 wt% LiNO3. Although Figure 8D and 8E The fringes in the image are suitable for measurement using advanced image processing methods, but due to increased sodium ion exchange, the contrast or critical angle transition of the fringes decreases, which reduces the refractive index. Not limited to theory, as in... Figure 8D and 8E As observed, when the sodium concentration exceeds approximately 10% by weight of NaNO3, the potassium streaks begin to fade. This is because sodium undergoes rapid ion exchange with lithium, and compared to potassium's ion exchange with sodium, which increases the refractive index, it decreases the refractive index of the surface layer much more quickly. Figure 8D The samples also underwent a longer processing time (16 hours) to obtain the same results as those processed for 12 hours. Figure 8CThe diagram shown is a similar diagram.

[0147] Also measured for Figures 8A-8C The compressive stress and maximum central tension of each sample, and the maximum central tension value is within... Figures 8A-8C The corresponding diagram is shown. For example... Figure 8A As shown, compared to the maximum central tension of glass-ceramic products treated with KNO3 / NaNO3 / LiNO3 ( Figure 8B and 8C The maximum center tension of glass-ceramic articles treated with a pure KNO3 / LiNO3 salt bath was low (27 MPa), with pressures of 71 MPa and 84 MPa respectively. However, the maximum center tension of the samples treated with a pure KNO3 / LiNO3 salt bath was low (27 MPa). Figure 8D and 8E This yielded a deep sodium distribution curve that extended beyond the peak center tension, resulting in lower compressive stress values.

[0148] Example 2 Prior to ion exchange strengthening, the concentrations of various components of the glass network in the glass-ceramic article (e.g., glass forming agents such as SiO2 and B2O3, intermediate substances such as Al2O3, modifiers such as CaO, Na2O, etc.) are distributed substantially uniformly across the thickness of the glass-ceramic article from its outer surface. For example, the glass-ceramic article includes one or more glass forming agents, and the concentration of the glass forming agent is substantially constant across the entire thickness of the glass-ceramic article. Furthermore, the glass-ceramic article includes one or more modifiers, such as Na2O and / or another alkali metal oxide, and the concentration of the modifier is substantially constant across the entire thickness of the glass-ceramic article.

[0149] However, after ion exchange, the concentration of alkali metal oxides (e.g., K₂O) in the glass-ceramic article varies depending on the depth from the outer surface of the article. To determine the effect of single-stripe ion exchange treatment on the glass-ceramic article, a glass-ceramic article formed of composition A with a thickness of 0.8 mm was subjected to single-stripe ion exchange treatment for 16 hours at 500 °C in a bath containing 80 wt% KNO₃, 20 wt% NaNO₃, and 0.1 wt% LiNO₃ (single-stripe example). Another glass-ceramic article formed of composition A with a thickness of 0.8 mm was subjected to conventional ion exchange treatment for 12 hours at 470 °C in a bath containing 30 wt% KNO₃, 70 wt% NaNO₃, and 0.05 wt% LiNO₃, followed by treatment for 1 hour at 470 °C in a bath containing 30 wt% KNO₃ and 70 wt% NaNO₃ (conventional 10x example). The concentration distribution of various components in the glass, such as alkali metals, was measured using electron probe microanalysis (EPMA), and the distribution curves are shown below. Figure 9 .

[0150] Specifically, for both single stripe (902) and conventional IOX treatment (904), the concentration of K2O decreases from the surface of the glass-ceramic article to 0 mol% in the direction of the center line CL of the glass-ceramic article.

[0151] The Na₂O concentration (906) initially increases and then decreases from the surface of the glass-ceramic article along the direction of the centerline CL of the single-stripe IOX. That is, the Na₂O concentration 904 in the glass-ceramic article, varying with distance from the surface, initially has a positive slope but then a negative slope. In various embodiments, the difference between the surface Na₂O concentration and the minimum Na₂O concentration is less than 5 mol%, and the surface Na₂O concentration is less than 10 mol%. In various embodiments, the Na₂O concentration is greater than 0 mol% throughout the entire thickness of the ion-exchange glass-ceramic article. For example, in various embodiments, the Na₂O concentration is greater than 0 mol% and less than 2.5 mol%.

[0152] In contrast, the Na₂O concentration of glass-ceramic articles treated with conventional IOX (908) exhibits a surface peak, decreasing and diminishing from the surface along the centerline CL of the glass-ceramic article. Therefore, as can be seen from the comparison of 906 and 908, the single-stripe IOX treatment significantly reduces the amount of sodium near the surface (approximately 2.5 mol% vs. approximately 20 mol%), but the sodium distribution at depths exceeding approximately 80 µm (which contributes to damage resistance) is comparable to that of conventional IOX treatment, indicating a deep compressibility depth.

[0153] In addition, Figure 9 In the embodiment, the Li2O concentration (910) of a glass-ceramic article subjected to a single stripe 10X increases from the surface Li2O concentration to the maximum Li2O concentration at the center line CL as the distance increases. In various embodiments, the difference between the surface Li2O concentration and the maximum Li2O concentration is less than 5 mol%. In various embodiments, the maximum Li2O concentration is 19 mol% to 32 mol%. In contrast, the Li2O concentration (912) of a glass-ceramic article subjected to a conventional 10X increases sharply near the surface, and then continuously increases from the surface Li2O concentration to the maximum Li2O concentration at the center line CL as the distance increases. However, the difference between the surface Li2O concentration and the maximum Li2O concentration is greater than 10 mol%, greater than 15 mol%, or even greater than 18 mol%.

[0154] Although the concentration of alkali metal oxides in glass-ceramic articles is altered due to ion exchange strengthening, it should be understood that the concentrations of other components of the glass network [e.g., glass forming agents, intermediates, and immobile modifiers such as alkaline earth metal oxides (CaO, MgO, etc.)] remain substantially constant (e.g., substantially uniform across the thickness of the glass-ceramic article). Example 3 To further increase the center tension of glass-ceramic articles treated with single-stripe IOX, a two-step ion exchange process was developed. The articles in Example 3 were all formed from composition A. Figures 10A-10H The FSM pattern of a glass-ceramic article subjected to single-stripe IOX treatment is shown. Specifically, Figures 10A-10H Each of the glass-ceramic articles formed from composition A and subjected to ion exchange treatment is shown with a 365 nm FSM spectrum.

[0155] exist Figure 10A In one process, glass-ceramic articles were treated at 500 °C for 12 hours with a mixture containing 90 wt% KNO3, 10 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic articles exhibited a maximum central tensile strength of 84 MPa. Then, the glass-ceramic articles were treated at 500 °C for 4 hours with a mixture containing 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic articles exhibited a maximum central tensile strength of 103 MPa. This can be compared with... Figure 10A and Figure 10B As shown, the first step demonstrates the formation of well-defined stripes ( Figure 10A The second step increases sodium ion exchange and increases center tension (including maximum center tension). Figure 10BHowever, after the second step, the stripes begin to lose contrast (or “fade”) due to increased sodium ion exchange, which reduces the refractive index of the surface layer.

[0156] exist Figure 10C In one process, the glass-ceramic product was treated at 500 °C for 12 hours with a solution containing 95 wt% KNO3, 5 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic product exhibited a maximum central tensile strength of 71 MPa. Then, the glass-ceramic product was treated at 500 °C for 4 hours with a solution containing 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic product exhibited a maximum central tensile strength of 98 MPa. Figure 10A and Figure 10B Similarly, the first step showed the formation of good stripes ( Figure 10C The second step increases sodium ion exchange and increases center tension (including maximum center tension). Figure 10D Similarly, after the second step, the stripes begin to lose contrast (or “fade”) due to increased sodium ion exchange, which reduces the refractive index of the surface layer.

[0157] exist Figure 10E In this process, the glass-ceramic product was treated at 500 °C for 7 hours with a mixture containing 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic product exhibited a maximum central tensile strength of 100 MPa. Then, the glass-ceramic product was treated at 500 °C for 4 hours with a mixture containing 93 wt% KNO3, 7 wt% NaNO3, and 0.1 wt% LiNO3. Figure 10F The resulting glass-ceramic product exhibits a maximum central tensile strength of 95 MPa. The high concentration of sodium salt in the first step generates compressive stress with a deep DOC (distilled charge). Figure 10E During the second step, potassium streaks were formed. Figure 10F ), which includes high concentrations of potassium salts.

[0158] exist Figure 10G In one process, the glass-ceramic product was treated at 500 °C for 6 hours with a mixture containing 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic product exhibited a maximum central tensile strength of 103 MPa. Then, the glass-ceramic product was treated at 500 °C for 5 hours with a mixture containing 90 wt% KNO3, 10 wt% NaNO3, and 0.1 wt% LiNO3. The resulting glass-ceramic product exhibited a maximum central tensile strength of 101 MPa. Figure 10E and 10FSimilarly, the sodium salt concentration in the first step generates compressive stress with a deep DOC ( ). Figure 10G During the second step, potassium streaks were formed. Figure 10H ), which includes high concentrations of potassium salts.

[0159] Example 4 Glass and glass-ceramic products were subjected to one of various ion exchange treatments, and their resistance to damage was measured. Table 2 below provides the ion exchange conditions, stress distribution curve characteristics, and strength (fracture) test values. All samples were 0.8 mm thick.

[0160] Sample A is a glass article with the following nominal composition and subjected to conventional IOX treatment, wherein the nominal composition (in mol%) is 71 SiO2; 1.9 B2O3; 12.8 Al2O3; 2.4 Na2O; 8.2 Li2O; 2.9 MgO; 0.8 ZnO; 0.02 Fe2O3; 0.01 ZrO2; 0.06 SnO2. The fracture toughness of Sample A obtained by the double cantilever beam method is 0.84 MPa√m. Sample B is a glass article with the following nominal composition and subjected to conventional IOX treatment, wherein the nominal composition (in mol%) is 58.4 SiO2; 6.1 B2O3; 17.8 Al2O3; 1.7 Na2O; 0.2 K2O; 10.7 Li2O; 4.4 MgO; 0.6 CaO; 0.02 Fe2O3; 0.01 ZrO2; 0.08 SnO2. Sample B exhibits a fracture toughness of 0.95 MPa√m obtained using the double cantilever beam method. Sample C is a glass-ceramic article formed from composition A and subjected to a conventional two-step IOX treatment. Sample D is a glass-ceramic article formed from composition A and subjected to a single-stripe IOX treatment according to various embodiments. Sample E is a glass-ceramic article formed from composition A and subjected to a two-step single-stripe IOX treatment according to various embodiments. Sample F is a glass-ceramic article formed from composition A and subjected to different two-step single-stripe IOX treatments according to various embodiments. Sample G is a glass-ceramic article formed from composition A and subjected to different two-step single-stripe IOX treatments according to various embodiments.

[0161] Table 2:

[0162] The strength reported as fracture in Table 2 was measured using a four-point bending test after damage was introduced into the glass, by applying a fracture stress that led to failure, the damage being introduced via a slapper using 80-grit sandpaper impact with 1.3 J of energy. This method is described in US20190072479A1. The test was performed using an apparatus based on a dynamic impact test, comprising a pendulum with a surface ranging from flat to curved, wherein a glass-ceramic test specimen was mounted onto the pendulum and then used to bring the test specimen into contact with a roughened impact surface. This apparatus is described in more detail in International Application Publication No. WO2017100646, which is incorporated herein by reference in its entirety. For the test, the sample was loaded onto a rack and then pulled back from the pendulum's equilibrium position (to a position where 1.3 J of energy would be applied to the specimen to be tested) and released to create a dynamic impact on the impact surface. The impact surface included an abrasive disc attached to the impact surface, which was in the form of sandpaper and had a grit number specified in the examples. Cut the sandpaper into 25 mm square pieces. If the pieces bend during the cutting process, flatten the sandpaper.

[0163] The radius of curvature of the curved surface on the substrate is selected to provide a bending tensile force of 100 MPa when the substrate is bent around the curved surface, such that the tensile force is an externally applied tensile force caused by the stress of the bent substrate.

[0164] Example 5 Next, the glass-ceramic articles formed from composition A were subjected to ion exchange treatment, and their stress distribution curves were measured using RNF. The results are shown in... Figure 11Glass-ceramic products formed from composition A and treated with 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3 at 500 °C for 10 hours, followed by single-stripe ion exchange treatment with 93 wt% KNO3, 7 wt% NaNO3, and 0.1 wt% LiNO3 at 500 °C for 5 hours (identical to sample G in Table 2) exhibit stress distribution curve 1102. Glass-ceramic products formed from composition A and treated with 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3 at 500 °C for 7 hours, followed by single-stripe ion exchange treatment with 93 wt% KNO3, 7 wt% NaNO3, and 0.1 wt% LiNO3 at 500 °C for 5 hours (identical to sample F in Table 2) exhibit stress distribution curve 1104. Glass-ceramic articles (identical to sample C in Table 2) formed from composition A and treated with a bath containing 30 wt% KNO3, 70 wt% NaNO3 and 0.05 wt% LiNO3 at 470 °C for 12 hours, followed by conventional ion exchange treatment with 30 wt% KNO3 and 70 wt% NaNO3 at 470 °C for 1.5 hours, exhibit stress distribution curve 1106. Figure 11 As shown, the stress in distribution curves 1102 and 1104 decreases from compressive stress to tensile stress as the distance from the outer surface of the glass-ceramic product increases.

[0165] The stress distribution curve of the glass-ceramic product with a low refractive index layer (1106) from the surface to 0.1 t Or at depths greater than 80 MPa, there are high compressive stresses (e.g., above 80 MPa). t This refers to the thickness of the glass-ceramic material. However, stress distribution curves 1102 and 1104 show values ​​exceeding 120 µm or 0.15 µm. t There is increased compressive stress at a depth of [insert depth here]. Specifically, this increased compressive stress is the following compressive stress: at 0.15 [insert depth here]. t At a depth greater than or equal to 40 MPa, at 0.19 t At a depth greater than or equal to 30 MPa, at 0.19 t The compressibility at a depth is greater than or equal to 20 MPa. Furthermore, stress distribution curves 1102 and 1104 exhibit significantly higher compressibility depths, exceeding 0.20 MPa. t 0.21 t Or 0.22 t .

[0166] Stress distribution curves 1102 and 1104 also include a defined knee stress CS kIt appears in the depth range following the peak. Not bound by theory, it is believed that the knee stress is caused by the potassium concentration stabilizing to the same level as inside the sample. CS k The value is between 100 and 150 MPa. It should be understood that CS... k It can be 100 MPa to 150 MPa, 100 MPa to 140 MPa, 100 MPa to 130 MPa, 100 MPa to 120 MPa, 100 MPa to 110 MPa, 110 MPa to 150 MPa, 110 MPa to 140 MPa, 110 MPa to 130 MPa, 110 MPa to 120 MPa, 120 MPa to 150 MPa, 120 MPa to 140 MPa, 120 MPa to 130 MPa, 130 MPa to 150 MPa, 130 MPa to 140 MPa, 140 MPa to 150 MPa, or any and all subranges formed by any of these endpoints. For example, in embodiments with a slightly lower LiNO3 content (e.g., 0.09 wt%, 0.08 wt%, or 0.07 wt%) in the final ion exchange step, a higher CS can be obtained without forming a low refractive index layer on the surface. k value.

[0167] In various implementations, CS is greater than 70 MPa, 80 MPa, or even 90 MPa. k The value provides enhanced fracture resistance during drop events on moderately rough surfaces. Not limited to theory, it is believed that tensile stresses of, for example, 70 MPa and 80 MPa can occur near the surface and at depths up to 30-40 µm during a drop from a height of 1 m or higher onto a rough surface. Accordingly, in various embodiments, the CS of the ion-exchange glass-ceramic article... k The value is greater than 70 MPa. In various implementations, CS... k Measurements were performed using birefringence measurements of the critical angle transition in prism-coupled (FSM) spectroscopy, where birefringence and CS... k Directly related.

[0168] like Figure 11 As shown, stress distribution curves 1102 and 1104 also reveal surface spikes in compressive stress. Without being bound by theory, these surface spikes are considered to be due to increased potassium ion concentration rather than sodium ion concentration. Specifically, in these samples, potassium permeation drops from approximately 5 µm to approximately 12 µm, which is correlated with low potassium concentrations and single-stripe FSM patterns for each polarization.

[0169] exist Figure 11The surface stresses visible in the charts are considered inaccurate because the resolution of the near-field refractive (RNF) method is limited, restricting the accuracy of representing peaks when stress changes significantly over very small distances. Therefore, in various embodiments, prism-coupled measurements are used whenever possible to measure or estimate surface stresses. When a low-refractive-index surface layer is avoided but the surface is rich in potassium ions, the average compressive stress in the peak regions corresponding to stress distribution curves 1102 and 1104 is approximately 150 MPa to about 300 MPa, while the surface stress is approximately 200 MPa to about 490 MPa. The upper limit is determined by subjecting the sample to a significantly longer ion exchange to obtain a double-fringe spectrum, measuring the surface compressive stress using conventional methods for measuring surface compressive stress via double-fringe spectroscopy, and then correcting for the decrease in compressive stress due to the excessively long ion exchange time. Beyond theoretical limitations, surface compressive stress and center tension (including maximum center tension) are sensitive to the amount of LiNO3 in the bath, with compressive stress decreasing from 400-490 MPa at LiNO3 concentrations of 0.05-0.07 wt% to 350-450 MPa at 0.07-0.12 wt% and further to 250-400 MPa at higher LiNO3 concentrations. It should be understood that specific compressive stress values ​​vary within a range depending on the Na / K ratio in the bath, with the highest values ​​obtained for baths with low NaNO3 concentrations (e.g., <5 wt%) and high KNO3 concentrations (e.g., >95 wt%) in the final ion exchange step.

[0170] Furthermore, stress distribution curves 1102 and 1104 exhibit very small second derivatives in the region between the bottom of the potassium-rich surface peak and a depth substantially exceeding the compression depth. This essentially linear region extends to greater than 0.25. t Up to 0.4 t The depth. For example, such as Figure 11 As shown, the basic linear region of the distribution curve exceeds 200 µm, even exceeding 240 µm, 280 µm, or even 320 µm. The starting point of the basic linear region is less than 50 µm, and depending on the specific implementation, it can be seen as low as 35 µm, 20 µm, 15 µm, or even 10 µm. In contrast, stress distribution curve 1106 is in the first 0.1... t Or it has an extremely high second derivative at 80µm. The short term "fundamentally linear" means that the absolute value of the second derivative of the stress distribution curve in the region of interest does not exceed a limit proportional to the average slope of that region, wherein the limit is 10 inverse mm. In some embodiments, to obtain a better approximation of the linear distribution curve segment, the limit may be set to 9, 8, 7, 6, or 5 inverse mm.

[0171] Between 20 and 240 µm (0.025) t Up to 0.3 t Within the depth range of ), the average slope of the stress distribution curve 1102 is approximately 580 MPa / mm, while the second derivative remains between -3000 and 3000 MPa / mm. 2 Between. Therefore, within the specified depth range, the ratio of the absolute value of the second derivative to the absolute value of the first derivative is less than 6. Between 40 and 200 µm (0.05 t Up to 0.25 t Within the depth range of ), this ratio is less than 5.

[0172] In various implementations, the second derivative in the region of interest is estimated by obtaining a tight polynomial fit to the distribution curve in the region of interest and then taking the derivative of the polynomial fit. This method can reduce or even eliminate the noise that typically occurs when directly calculating the second derivative of the experimental distribution curve using finite differences. However, in some implementations, it may be difficult to obtain a tight polynomial fit (e.g., R0). 2 (Polynomial fitting greater than or equal to 0.999). In such embodiments, another aspect of the essentially linear segment can be considered, for example, the local slope does not change significantly within the segment. For example, in the region of interest, the slope of stress distribution curve 1102 is not less than 470 MPa / mm and does not exceed 640 MPa / mm; therefore, the slope with a total variation of less than 170 MPa / mm does not exceed 30% of the average slope of the region. Thus, in some embodiments, "essentially linear" means that the total variation of the slope does not exceed 30%, 25%, 20%, or 15% of the average slope.

[0173] The average slope of stress distribution curve 1104 in the deep region of interest (excluding the peak region) is slightly higher than that of stress distribution curve 1102. Specifically, the average slope is 600 to 670 MPa / mm. Similar to stress distribution curve 1102, depending on the specific conditions under which the essentially linear distribution curve is observed, the essentially linear region of stress distribution curve 1104 extends from a lower limit of 30 µm, 25 µm, 20 µm, or 15 µm to an upper limit of 320 µm, 300 µm, 280 µm, 240 µm, or 200 µm. The upper limit represents most of the thickness (e.g., 0.25). t 0.3 t 0.35 t 0.37 t、 Or even 0.4 t Therefore, in various embodiments, the stress distribution curve of the ion-exchange glass-ceramic article has a substantially linear region that spans 0.02. tUp to 0.4 t The range, and the width is greater than 0.25. t Or 0.3 t This is true even when the conditions for observing a basically linear distribution curve are most stringent.

[0174] Stress distribution curves 1102 and 1104 also show peak center tension (which is the maximum center tension in the illustrated embodiments) ranging from 60 MPa to 120 MPa. In some embodiments, the peak center tension is less than 108 MPa or 102 MPa. Without being bound by theory, it is believed that peak center tension values ​​less than 120 MPa, or even 108 MPa, can reduce or eliminate the formation of low-refractive-index surface layers and / or chemical durability problems. It is also believed that reducing the LiNO3 content from 0.1 wt% to 0.09 wt%, 0.08 wt%, or even 0.07 wt% can increase the peak center tension. Furthermore, it is believed that higher center tension levels (including higher maximum center tension) can be obtained through more careful control of the composition of the ion exchange bath, particularly the LiNO3 content.

[0175] like Figure 11 As shown, stress distribution curves 1102 and 1004 also exhibit stresses ranging from 9.9 to 12.5 MPa in each compression region. The depth integral of the compressive stress was calculated over a thickness of 0.8 mm, and the average stress in the compressive region ranged from 52 MPa to 66 MPa. For both stress distribution curves 1102 and 1004, the total compressive stress integral in these two compressive regions ranged from 23.5 MPa to 31.3 MPa when divided by a thickness of 0.8 mm. However, when the LiNO3 content in the ion exchange bath decreased to 0.06–0.09 wt%, the stress increased to as high as 16 MPa. A slightly higher stress integral of mm is possible, and an 8 MPa pressure was achieved due to the increased LiNO3 content in the bath caused by ion exchange of multiple components. The stress integral is slightly lower than that in mm. Therefore, by changing the LiNO3 content of the bath, the average compressive stress in the compression region can vary from 85 MPa (when the LiNO3 level is 0.06-0.08 wt%) to 45 MPa (when the LiNO3 level is 0.2 to 0.3 wt%). In various embodiments, the total compressive stress integral of the two compression regions (e.g., near each opposite surface of the glass-ceramic article) is 20 MPa to 40 MPa when divided by the thickness of the glass-ceramic article. It should be understood that due to the force balance between the compression and tension regions, the same value and range of the thickness-normalized stress will apply to the thickness-normalized stress integral in the tension region.

[0176] Example 6 Glass-ceramic articles were subjected to various stripe-free ion exchange treatments, and their stress distribution curves were measured using RNF. Specifically, stress distribution curve 1202 corresponds to a glass-ceramic article formed from composition A and treated at 500 °C with 60 wt% KNO3, 40 wt% NaNO3, and 0.1 wt% LiNO3 for 8 hours. Stress distribution curve 1204 corresponds to a glass-ceramic article formed from composition A and treated at 470 °C with 70 wt% KNO3, 30 wt% NaNO3, and 0.1 wt% LiNO3 for 8 hours (sample O below). Stress distribution curve 1206 corresponds to a glass-ceramic article formed from composition A and treated at 470 °C with 70 wt% KNO3, 30 wt% NaNO3, and 0.1 wt% LiNO3 for 13 hours (sample P below). Finally, stress distribution curve 1208 corresponds to a glass-ceramic article formed from composition A and treated with conventional ion exchange treatment (the same as sample C in Table 2), which includes a first step of treatment at 470 °C with 30 wt% KNO3, 70 wt% NaNO3 and 0.05 wt% LiNO3 for 12 hours, and a second step of treatment at 470 °C with 30 wt% KNO3 and 70 wt% NaNO3 for 1.5 hours.

[0177] like Figure 12 As shown, each stress distribution curve includes a compression depth of approximately 20% of the thickness of the glass-ceramic article (0.8 mm per sample). The CS(z) of stress distribution curve 1202 generally has a positive second derivative, but it also includes a substantially linear region extending from 50 µm to a depth of 240 µm (0.05). t Up to 0.3 t ), or more precisely, from 56µm to 208µm (0.07 t Up to 0.26 t The average stress slope in the basically linear region is approximately 1000 MPa / mm, and the compression depth is approximately 0.17 mm (0.21). t The maximum central tension is 107 MPa. Stress distribution curve 1202 also exhibits a high CS of 210 to 220 MPa. k Furthermore, the depth integral of the compressive stress in the compression region is equal to 16 MPa. mm. The tensile stress integral in the tensile region is 32 MPa. The thickness is mm, which balances the sum of the depth integrals of the compression regions on both sides of the tension region. The ratio of the total compressive stress integral to the thickness is 40 MPa. Furthermore, the average compressive stress in the compression region is 94 MPa, obtained by dividing the depth integral from z=0 to DOC (0.17 mm for stress distribution curve 1202) at the surface by the depth range from 0 to DOC. This average compressive stress remains essentially constant when the distribution curve is scaled with thickness (e.g., by shortening the ion exchange time, which is proportional to the square of the thickness).

[0178] like Figure 12 As shown, stress distribution curve 1204 is further characterized by a continuous positive second derivative throughout the entire compression region of the glass-ceramic article and through most of the tensile region on the interior. The integral of the compressive stress in each compression region is 15.6 MPa. mm. The total stress integral (which is either compressive or tensile stress due to stress balance) divided by the thickness (0.8 mm) is 39 MPa. The average compressive stress in the compression zone is 99.4 MPa, and as mentioned above, it remains essentially unchanged when the distribution curve scales with thickness.

[0179] The stress distribution curve 1204 typically has a higher absolute value of the second derivative, and it has a small portion (from about 80 µm to about 200 µm, or from 0.1 µm) t Up to 0.25 t The stress distribution curve 1204 is essentially linear. Compared to stress distribution curve 1202, stress distribution curve 1204 also exhibits slightly lower compressive stress at depths exceeding 60 µm and higher compressive stress at depths below 50 µm.

[0180] However, for the first 200 µm (or 0.25 µm) t The function CS(z) of stress distribution curves 1202 and 1204 both have the highest second derivative, which appears in the first 50 µm (or 0.06 µm). t More specifically, excluding the potassium-rich region of the first 10 µm, the highest second derivative occurs between depths of 12 µm and 40 µm. Compared to the highest second derivative of stress distribution curve 1208, the highest second derivatives of stress distribution curves 1202 and 1204 are significantly smaller (stress distribution curve 1202 is 25,000 to 40,000 MPa / mm). 2 The stress distribution curve 1204 ranges from 40,000 to 70,000 MPa / mm. 2The highest second derivative of stress distribution curve 1208 in the first 50 µm is twice or greater than that of stress distribution curve 1204. It should be understood that even higher second derivatives, such as up to 100,000 MPa / mm, can be obtained when the LiNO3 concentration in the final ion exchange step is below 0.1 wt%. 2 Furthermore, when the LiNO3 concentration is greater than 0.06 or 0.07 wt% and less than 0.1 wt%, the second derivative can be obtained without forming a low refractive index surface layer.

[0181] Stress distribution curves 1202 and 1204 can also be characterized by the slope range observed in the compression zone. In each embodiment, the surface slope of the potassium-rich region at a depth of approximately 10 µm is not included. Specifically, the CS of stress distribution curve 1202... k The stress distribution curve 1204 exhibits a maximum central tension of 210 to 220 MPa, with the negative slope of CS(z) monotonically changing from -2650 MPa / mm in the depth range of 10 to 20 µm to approximately -1430 MPa / mm at a depth of 50 µm. The negative slope of CS(z) then changes more slowly to -880 MPa / mm at a DOC of 170 µm. Stress distribution curve 1204 begins with a higher slope of approximately -3830 MPa / mm in the depth range of 10 to 20 µm, changes rapidly to approximately -1610 MPa / mm at a depth of 50 µm, then changes slowly and reaches approximately -950 MPa / mm at a DOC of 157 µm. Stress distribution curve 1202 has a maximum central tension of 107 MPa, while stress distribution curve 1204 has a significantly lower maximum central tension of 77 MPa.

[0182] Stress distribution curves 1202 and 1204 each exhibit stress distribution at approximately 40 µm (0.05). t At the first depth of ) and 120 µm (0.15 t The second depth also exhibits very high compressive stress, with the compressive stress exceeding 100 MPa at the first depth and exceeding 30 MPa at the second depth. Beyond theoretical considerations, this is believed to provide significant protection against higher stress events acting on shallow to medium-depth defects and lower to medium stress events acting on deep defects.

[0183] The stress distribution curve 1206 has a DOC of 0.17 mm, and the depth integral of the compressive stress in each compression region is equal to 14.4 MPa. mm. The average compressive stress in the compression zone is 84.7 MPa, and the total stress integral divided by the thickness (0.8 mm) is 36 MPa. Except for the potassium-rich surface layer, stress distribution curve 1206 exhibits the same characteristics as... Figure 11The stress distribution curves 1102 and 1104 exhibit similar characteristics, differing only in having a slightly smaller DOC. Specifically, similar to stress distribution curves 1102 and 1104, stress distribution curve 1206 has an extended, essentially linear region, indicating that the stripe-free ion exchange treatment described herein can provide a similar stress distribution and therefore similar fracture resistance, thus eliminating the need for single-stripe spikes for quality control. Furthermore, compared to stress distribution curves 1102 and 1104, stress distribution curve 1206 has a significantly higher CS at approximately 170 MPa. k Therefore, the average compressive stress in the compression region of stress distribution curve 1206 is slightly higher than that of stress distribution curves 1102 and 1104, which have higher DOC.

[0184] Example 7 Glass and glass-ceramic products were subjected to one of various ion exchange treatments, and their resistance to damage was measured. Table 3 below provides the ion exchange conditions, stress distribution curve characteristics, and strength (fracture) test values.

[0185] Sample H is a glass article having the same properties as Sample A and undergoing the same ion exchange conditions. Sample I is a glass article having the same properties as Sample B and undergoing the same ion exchange conditions. Sample J is a glass-ceramic article formed from composition A and subjected to a conventional two-step IOX treatment (same as Sample C). Samples K, L, and M are glass-ceramic articles formed from composition A and subjected to a stripe-free IOX treatment of 4, 8, or 12 hours, respectively, according to various embodiments. Samples N, O, P, and Q are glass-ceramic articles formed from composition A and subjected to different stripe-free IOX treatments of 4, 8, 13, or 16 hours, respectively, according to various embodiments. Samples R, S, and T are glass-ceramic articles formed from composition A and subjected to different stripe-free IOX treatments of 4, 8, or 16 hours, respectively, according to various embodiments.

[0186] Table 3:

[0187] The strengths reported as fracture in Table 3 were measured using a four-point bending test after damage was introduced into the glass, by applying a fracture stress that led to failure. This damage was introduced via a rubbery device using 80-grit sandpaper impact at 1.3 J. The method is described in US20190072479A1. The fracture strengths of samples J, K, L, and M are plotted as follows: Figure 13Samples J through T (manufactured from composition A) did not form an easily degradable low-refractive-index layer, but were still significantly superior to comparative examples H and I, despite the absence of a low-refractive-index layer. Compared to the glass examples of samples H and I, these samples (J through T) exhibited mechanical properties closer to the strength of the glass-ceramic dual-ion-exchange sample (sample J) with resistance to surface degradation.

[0188] Example 8 Glass and glass-ceramic products were subjected to one of various ion exchange treatments, and their damage resistance was measured using a drop test. The results are shown in... Figures 14A-14C In this embodiment, a glass-based article of the U-BB is mounted on an identical disc assembly, wherein the size, shape, and weight of the disc are adjusted to simulate a mobile phone device. As used herein, the term "glass-based" means any material comprising at least a portion of glass, including glass and glass ceramics. The disc is dropped horizontally onto 180-grit sandpaper in increments of 20 cm, with the glass-based material facing down—a flat drop. If the glass-based article remains intact after a drop from a certain height (e.g., 20 cm), the disc is dropped again from larger heights in 10 cm increments (e.g., 30 cm, 40 cm, 50 cm, etc.), up to a maximum height of 225 cm. The intact glass-based article is then dropped onto 80-grit sandpaper (in the same mobile phone device). Figures 14A-14C The height at which glass-based products fail on both 180-grit and 80-grit sandpaper was plotted.

[0189] Figure 14AThe results of incremental plane drop tests on 80-grit sandpaper are shown for samples U, V, W, and X. Sample U is a glass article formed from the following nominal composition, which, in mol%, contains: 63.6 SiO2; 2.3 B2O3; 15 Al2O3; 9.3 Na2O; 5.9 Li2O; 1.2 ZnO; 0.05 SnO2; 2.53 P2O5. The fracture toughness of sample U obtained by the double cantilever beam method is 0.76 MPa√m. Sample V is a glass article formed from the following nominal composition, which, in mol%, contains: 71 SiO2; 1.9 B2O3; 12.8 Al2O3; 2.4 Na2O; 8.2 Li2O; 2.9 MgO; 0.8 ZnO; 0.02 Fe2O3; 0.01 ZrO2; 0.06 SnO2. Sample V exhibits a fracture toughness of 0.84 MPa√m obtained using the double cantilever beam method. Sample W is a glass article formed from the following nominal composition, which, in mol% terms, contains: 58.4 SiO2; 6.1 B2O3; 17.8 Al2O3; 1.7 Na2O; 0.2 K2O; 10.7 Li2O; 4.4 MgO; 0.6 CaO; 0.02 Fe2O3; 0.01 ZrO2; and 0.08 SnO2. Sample W exhibits a fracture toughness of 0.95 MPa√m obtained using the double cantilever beam method. Sample X is a glass article formed from composition A. Samples U, V, W, and X were each subjected to conventional ion exchange treatments, including a first step of treatment at 380 °C for 4 hours in a bath containing 70 wt% NaNO3 and 30 wt% KNO3, and a second step of treatment at 380 °C for 40 minutes in a bath containing 7 wt% NaNO3 and 93 wt% KNO3.

[0190] Figure 14B and 14CThe results of incremental plane drop tests on 180-grit and 80-grit sandpaper are shown. Samples Y, Z, AA, and BB were each formed from composition A. Sample Y underwent a conventional two-step ion exchange treatment, comprising a first step of treatment at 470 °C with 70 wt% NaNO3, 30 wt% KNO3, and 0.05 wt% LiNO3 for 12 hours, followed by treatment at 470 °C with 70 wt% NaNO3 and 30 wt% KNO3 for 1.5 hours (the same as in Line 1106 and Example 4C, and a conventional process similar to Example 2). Sample Z was subjected to a two-step stripe-free ion exchange treatment, consisting of a first step of treatment with 40 wt% NaNO3, 60 wt% KNO3, and 0.1 wt% LiNO3 at 500 °C for 6 hours, followed by treatment with 10 wt% NaNO3, 90 wt% KNO3, and 0.1 wt% LiNO3 at 500 °C for 5 hours (similar to line 1104, Example 4F). Sample AA was subjected to a single-step stripe-free ion exchange treatment with 40 wt% NaNO3, 60 wt% KNO3, and 0.1 wt% LiNO3 at 500 °C for 8 hours (same as Example 7L). Sample BB was subjected to a single-step stripe-free ion exchange treatment with 30 wt% NaNO3, 70 wt% KNO3, and 0.1 wt% LiNO3 at 470 °C for 8 hours (same as Example 7O and line 1204).

[0191] like Figures 14A-14C As shown, except for the two glass-based articles in Examples U and V, all others remained intact when dropped from a height of approximately 250 cm onto 80-grit sandpaper (providing an average intact drop height of 160 cm to 178 cm). Therefore, Figures 14A-14C The ion-exchange glass-ceramic articles described in this paper demonstrate statistically similar drop performance to glass articles chemically strengthened by ion exchange processes according to the prior art.

[0192] Example 9 To determine the effects of the stripeless ion exchange treatments of each embodiment on aging and corrosion, glass-ceramic articles were prepared and subjected to one of various ion exchange treatments. All glass-ceramic articles were formed from composition A. Table 4 below shows the ion exchange treatment conditions and accelerated aging test results. To determine the accelerated aging results, samples were placed in a chamber at 85°C and 85% relative humidity for a period of time (reported in Table 4), and corrosion was examined.

[0193] Table 4:

[0194] As shown in Table 4, the stripeless IOX treatment described in each embodiment yields significantly improved accelerated aging results.

[0195] To further investigate the effects of aging, optical micrographs of the CC of the samples were obtained before and after the samples underwent an accelerated aging test at 85 °C and 85% relative humidity for 144 hours. Figure 15A For the previous ones, Figure 15B (For later). Sample JJ was also obtained after 48 hours ( Figure 15C ) and 144 hours ( Figure 15D The optical micrograph shows that sample JJ is a glass-ceramic product formed from composition A and subjected to a striation-free ion exchange treatment, which consisted of treatment at 470°C with 90 wt% KNO3, 10 wt% NaNO3, and 0.1 wt% LiNO3 for 12 hours. As can be seen in the optical micrograph, sample CC exhibited severe corrosion after 144 hours, while... Figure 15C and 15D The sample JJ shown does not exhibit any visible corrosion.

[0196] SIMS depth distribution analysis was used to obtain the elemental depth distribution of samples CC and JJ within the first 300 nm depth. These distributions are shown in... Figure 16A and 16B .like Figure 16A As shown, sample CC formed a hydrated surface layer, in which sodium was consumed and reacted with atmospheric CO2. However, as Figure 16B As shown, no hydration layer was formed in sample JJ.

[0197] Through chemical strengthening, the various embodiments described herein can achieve improved glass-ceramic properties, such as improved damage resistance, improved chemical durability, and reduced corrosion when exposed to high humidity conditions. Additionally, the ion exchange treatment described herein enables the resulting glass-ceramic articles to include single stripes for FSM metrological quality control techniques, or to be stripe-free. The various embodiments described herein also provide additional or alternative quality control processes for use, for example, when stripes are not obtained by ion exchange treatment or when the glass-ceramic article is opaque.

[0198] The reinforced articles disclosed herein, such as ion-exchange glass-ceramic articles, can be incorporated into another article, such as articles having a display (or display article) [e.g., consumer electronics, including mobile phones, tablets, computers, navigation systems, wearable devices (such as watches), etc.]; building articles; transportation articles (e.g., automobiles, trains, aircraft, ships, etc.), appliance articles, or any article requiring a certain degree of transparency, scratch resistance, abrasion resistance, or a combination of the above properties. Figure 18A and 18BExemplary articles containing any of the reinforced articles disclosed herein are shown. Specifically, Figure 18A and 18B A consumer electronic device 1800 is shown, comprising a housing 1802 having a front surface 1804, a rear surface 1806, and a side surface 1808; electrical components (not shown) at least partially or completely located within the housing and including at least a controller, a storage device, and a display 1810, the display being located at or adjacent to the front surface of the housing; and a cover substrate 1812 located at or above the front surface of the housing such that the cover substrate 1812 is above the display. In some embodiments, at least one of the cover substrate 1812 or a portion of the housing 102 may comprise any of the reinforcing articles disclosed herein.

[0199] It will be apparent to those skilled in the art that various modifications and variations can be made to the embodiments described herein without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and variations of the various embodiments described herein, provided that such modifications and variations fall within the scope of the appended claims and their equivalents.

Claims

1. An ion-exchange glass-ceramic product having a thickness t, wherein: The ion-exchange glass-ceramic article is formed from a composition containing 20 mol% to 32 mol% Li2O; The glass-ceramic article includes stress, which decreases with increasing distance according to a basic linear function from a depth of about 0.07t to a depth of about 0.26t from the outer surface of the ion-exchange glass-ceramic article toward the centerline. The stress changes from compressive stress to tensile stress at a depth of about 0.18t to about 0.25t from the outer surface of the ion-exchange glass-ceramic article; The absolute value of the maximum compressive stress at the outer surface of the ion-exchange glass-ceramic article is 200 MPa to 350 MPa, and the absolute value of the maximum central tension is greater than 60 MPa to 160 MPa.

2. The ion-exchange glass-ceramic product according to claim 1, wherein, The fracture toughness of the ion-exchange glass-ceramic product is 1 MPa√m or greater, as measured by the double cantilever beam method.

3. The ion-exchange glass-ceramic product according to claim 1, wherein, The fracture toughness is 1 MPa√m to 1.5 MPa√m, as measured using the double cantilever beam method.

4. The ion-exchange glass-ceramic product according to claim 1, wherein, The maximum compressive stress is 1.8 to 2.2 times the maximum central tension.

5. The ion-exchange glass-ceramic product according to claim 1, wherein, The maximum center tension is 70 MPa or greater.

6. The ion-exchange glass-ceramic product according to claim 1, wherein, The maximum center tension is 80 MPa to 140 MPa.

7. The ion-exchange glass-ceramic product according to claim 1, wherein, The maximum compressive stress is between 180 MPa and 350 MPa.

8. The ion-exchange glass-ceramic product according to claim 1, wherein, The Na2O concentration on the outer surface of the ion-exchange glass-ceramic product is less than 10 mol.

9. The ion-exchange glass-ceramic article according to any one of claims 1-7, wherein, The ion-exchange glass-ceramic product comprises: 60 mol% to 72 mol% SiO2; Al₂O₃ greater than 0 mol% to 6 mol%; 0.7 mol% to 2.2 mol% of P2O5; and ZrO2 ranging from 1.7 mol% to 4.5 mol%.

10. A consumer electronics product comprising: A housing, the housing including a front surface, a rear surface and side surfaces; Electrical components, at least partially located within the housing, include a controller, a memory, and a display, the display being located on or near the front surface of the housing; as well as A cover plate substrate disposed above the display, wherein a portion of the housing or at least one of the cover plate substrates comprises an ion-exchange glass-ceramic article as claimed in any one of claims 1-7.

Citation Information

Patent Citations

  • Corrosion indicator for use with a piping system, and a piping system using the corrosion indicator

    US20190072479A1

  • Systems and methods for measuring a profile characteristic of a glass sample

    US8854623B2

  • Fusion-formable glass-based articles including a metal oxide concentration gradient

    WO2017100646A1